On-press development type printing plate precursor, method for producing printing plate, and printing method
The on-press development type printing original plate with a specific aluminum support and hydroxy acid compound composition effectively prevents edge staining and maintains image quality over time.
Patent Information
- Application Number
- JP2021574033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-15
- Filing Date
- 2021-01-25
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2041-01-25
AI Technical Summary
Existing on-press development type lithographic printing plates suffer from edge staining both immediately after manufacture and after aging, and there is a deterioration in image forming properties in the edge regions.
An on-press development type printing original plate with an aluminum support having an anodized film, featuring a sagging edge shape and a constituent layer containing a hydroxy acid compound with specific properties, including a molecular weight of 60 to 300 and solubility in water of 10 g/L or more, which maintains consistent compound content across the plate surface.
Prevents edge staining both during and after aging, while maintaining excellent image forming properties in the edge regions.
Smart Images

Figure 0007606473000033 
Figure 0007606473000034 
Figure 0007606473000035
Abstract
Description
[Technical field]
[0001] The present invention relates to an on-press development type printing plate precursor, a method for making a printing plate, and a printing method. [Background technology]
[0002] Generally, a lithographic printing plate consists of an oleophilic image area that accepts ink during the printing process and a hydrophilic non-image area that accepts dampening water. Lithographic printing utilizes the mutual repulsion properties of water and oil-based ink, making the oleophilic image area of the lithographic printing plate the ink-receptive area and the hydrophilic non-image area the dampening water-receptive area (ink-non-receptive area) to create a difference in ink adhesion on the surface of the lithographic printing plate, and after ink is applied only to the image area, the ink is transferred to the printing material such as paper to print.
[0003] Currently, in the platemaking process for producing lithographic printing plates from lithographic printing plate precursors, image exposure is performed using CTP (computer-to-plate) technology. In other words, image exposure is performed by scanning exposure directly onto the lithographic printing plate precursor using a laser or laser diode, without using a lithographic film.
[0004] On the other hand, due to the growing concern about the global environment, environmental problems associated with waste liquids from wet processes such as development processing have come into focus in relation to the production of lithographic printing plate precursors, and as a result, there has been a trend toward simplifying or eliminating development processing. As one of the simplified development processes, a method called "on-press development" has been proposed. On-press development is a method in which, after image exposure of a lithographic printing plate precursor, the plate is directly attached to a printing press without undergoing conventional wet development processing, and the non-image portion of the image recording layer is removed at an early stage of the normal printing process.
[0005] When printing using a lithographic printing plate, when printing on paper smaller than the size of the printing plate, as in a normal sheet-fed printing press, the edge of the printing plate is outside the paper surface, so the edge does not affect the print quality. However, when printing continuously on rolled paper using a rotary press, such as in newspaper printing, the edge of the printing plate is within the paper surface, so the ink adhering to the edge is transferred to the paper, causing linear stains (edge stains), which significantly reduces the commercial value of the printed matter.
[0006] In an attempt to suppress the occurrence of edge stains, a water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more contained in a region of the image recording layer side plate surface up to 5 mm inward from the edge of a lithographic printing plate precursor having an image recording layer on a support is contained in a region of the image recording layer side plate surface up to 5 mm inward from the edge of the image recording layer side plate surface, and the content per unit area of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more is 50 mg / m or more lower than the content per unit area of the water-soluble compound in the region other than the above region. 2 Many of the above-mentioned planographic printing plate precursors are disclosed in Patent Document 1. Patent Document 2 discloses an on-press development type lithographic printing plate precursor having an image recording layer on an aluminum support having an anodized film, the edge of the lithographic printing plate precursor having a drooped shape, the image recording layer having support adsorption properties, a molecular weight of 1,000 or less, and containing a compound having no unsaturated double bond group in the molecule, and the content of the compound is substantially the same within the plane of the image recording layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2016 / 052443 [Patent Document 2] International Publication No. 2019 / 044700 Summary of the Invention [Problem to be solved by the invention]
[0008] The above-mentioned Patent Document 1 describes polyols, betaines, organic sulfonates, organic sulfates, organic carboxylic acids or salts thereof, and amino acids as water-soluble compounds having a molecular weight of 60 to 300 and a solubility in water at 20° C. of 10 g / L or more. The lithographic printing plate precursor described in Patent Document 1 is characterized in that the content of the water-soluble compound in the edge regions is intentionally made higher than in areas other than the edge regions by, for example, applying a coating liquid containing the above-mentioned water-soluble compound only to the edge regions of the lithographic printing plate precursor. However, it has been found that a lithographic printing plate precursor that intentionally contains a large amount of a water-soluble compound in the edge region has a problem in that image forming properties are reduced in the edge region.
[0009] The above-mentioned Patent Document 2 describes an oxoacid as a compound that has support adsorption properties, has a molecular weight of 1,000 or less, and does not have an unsaturated double bond group in the molecule. Incidentally, on-press development type printing plate masters may be stored for a long period (e.g., 12 months) after production and then used for plate making. In such cases, that is, even after aging, it is desirable to be able to suppress the occurrence of the above-mentioned edge stains. However, in the on-press development type lithographic printing plate precursor described in Patent Document 2, it has been found that it is difficult to prevent the occurrence of edge stains even after aging.
[0010] The problem that the present invention aims to solve is to provide an on-press development type printing original plate that is prevented from edge contamination not only after production but also after aging, a method for making a printing plate using an on-press development type printing original plate, and a printing method using an on-press development type printing original plate. Furthermore, according to the present invention, it is possible to provide an on-press development type lithographic printing plate precursor in which deterioration of image formability in edge regions is suppressed. [Means for solving the problem]
[0011] The means for solving the above problems are described below. 。 [1 ] An on-press development type printing plate precursor having at least one constituent layer on an aluminum support having an anodized film, the on-press development type printing plate precursor having a drooped edge, the at least one constituent layer containing a hydroxy acid compound having two or more hydroxyl groups, a molecular weight of 60 to 300, and a content of a water-soluble compound having a solubility in water at 20°C of 10 g / L or more being substantially uniform within the plane of the constituent layer, The on-press development type printing plate precursor has an image recording layer, The on-press development type printing original plate has a protective layer, The on-press development type printing plate precursor has a layer containing the hydroxy acid compound as a protective layer. [ 2 ] The on-press development type printing plate precursor has an undercoat layer. 1 ] An on-press development type printing plate precursor described in the above. [ 3 ] The protective layer contains a polyvinyl alcohol resin. 1 ] Or [2] 2. An on-press development type printing plate precursor according to claim 1. [ 4 ] The image recording layer contains an infrared absorbing agent, a polymerization initiator, a polymerizable compound, and a polymer compound [1] to [ 3 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 5 ] The polymer compound is a polymer compound containing a structural unit derived from a styrene compound and / or a structural unit derived from an acrylonitrile compound. 4 ] An on-press development type printing plate precursor described in the above. [ 6 ] In the polymer compound containing the constitutional unit derived from the styrene compound and the constitutional unit derived from the acrylonitrile compound, the composition ratio of the constitutional unit derived from the styrene compound and the constitutional unit derived from the acrylonitrile compound is 4:1 to 1:4 [ 5 ] An on-press development type printing plate precursor described in the above. [ 7 ] The polymer compound is a polymer particle. 4 ]~[ 6 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 8 ] The polymer particles are thermoplastic particles. 7 ] An on-press development type printing plate precursor described in the above. [ 9 ] An on-press development type printing plate precursor having at least one constituent layer on an aluminum support having an anodized film, the on-press development type printing plate precursor having a drooped edge, the at least one constituent layer containing a hydroxy acid compound having two or more hydroxyl groups, a molecular weight of 60 to 300, and a content of a water-soluble compound having a solubility in water at 20°C of 10 g / L or more being substantially uniform within the plane of the constituent layer, The on-press development type printing plate precursor has a non-photosensitive layer, and all of the constituent layers are non-photosensitive, The on-press development type printing plate precursor has an undercoat layer. [ 10 ] The on-press development type printing plate precursor has a protective layer. 9 ] An on-press development type printing plate precursor described in the above. [ 11 ] The protective layer contains a polyvinyl alcohol resin. 10 ] An on-press development type printing plate precursor described in the above. [ 12 ] The layer containing the hydroxy acid compound is a non-photosensitive layer. 9 ]~[ 11 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 13 ] The layer containing the hydroxy acid compound is an undercoat layer. 9 ]~[ 11 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 14 ] The layer containing the hydroxy acid compound is a protective layer. 10 ] or [11 ] An on-press development type printing plate precursor described in the above. [ 15 ] The ClogP value of the hydroxy acid compound is 0.5 or less [1] to [ 14 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 16 ] The molecular weight of the hydroxy acid compound is 1,000 or less [1] to [ 15 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 17 ] The content of the hydroxy acid compound is 10 to 200 mg / m 2 [1]~[ 16 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 18 ] The arithmetic mean height Sa of the outermost layer surface on the side opposite to the side having the constituent layer containing the hydroxy acid compound is 0.3 to 20 μm [1] to [ 17 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 19 ] The arithmetic mean height Sa of the outermost layer surface on the side having the constituent layer containing the hydroxy acid compound is 0.3 to 20 μm [1] to [ 18 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 20 ] The average diameter of micropores on the surface of the anodized film is 10 to 100 nm, and the lightness L* value in the L*a*b* color system of the surface of the anodized film on the side of the constituent layer containing the hydroxy acid compound is 60 to 100 [1] to [ 19 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 21 ] The micropores in the anodized film are composed of large-diameter pores extending 10 nm to 1,000 nm in the depth direction from the surface of the anodized film, and small-diameter pores that communicate with the bottoms of the large-diameter pores and extend 20 nm to 2,000 nm in the depth direction from the communicating positions, the large-diameter pores having an average diameter of 15 nm to 100 nm on the surface of the anodized film, and the small-diameter pores having an average diameter of 13 nm or less at the communicating positions[1] to [ 20 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 22 ] The sagging shape of the edge of the on-machine development type printing plate master is a sagging amount X of 25 to 150 μm and a sagging width Y of 70 to 300 μm [1] to [ 21 ] The on-press development type printing plate precursor according to any one of the above items 1 to 5. [ 23 ] [1]~[ 8 and supplying at least one of printing ink and dampening water on a printing press to remove unexposed areas of the image recording layer in the image-exposed on-press development type printing plate precursor. [ 24 ] [ 9 ]~[ 14 13. A printing method comprising the steps of: supplying at least one of printing ink and dampening water to the on-press development type printing plate precursor described in any one of claims 1 to 7 on a printing press to remove the non-photosensitive layer in the on-press development type printing plate precursor to prepare a throwaway plate; and carrying out printing using the prepared throwaway plate. The present invention relates to the above-mentioned [1] to [ 24
[0023] This is an invention relating to the above-mentioned item, but other matters (for example, the following items (1) to (30)) are also described below.
[0012] (1) An on-press development type printing plate precursor having at least one constituent layer on an aluminum support having an anodized film, the edge of the on-press development type printing plate precursor having a drooped shape, and the at least one constituent layer contains a hydroxy acid compound having two or more hydroxyl groups, and the content of a water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20° C. of 10 g / L or more is substantially uniform within the plane of the constituent layer. (2) The on-press development type printing plate precursor according to (1), in which the ClogP value of the hydroxy acid compound is 0.5 or less. (3) The on-press development type printing plate precursor according to (1) or (2), wherein the molecular weight of the hydroxy acid compound is 1,000 or less. (4) The content of the hydroxy acid compound is 10 to 200 mg / m 2 The on-press development type printing plate precursor according to any one of (1) to (3), (5) The on-press development type printing plate precursor according to any one of (1) to (4), wherein the arithmetic mean height Sa of the outermost layer surface on the side opposite to the side having the constituent layer containing the hydroxy acid compound is 0.3 to 20 μm. (6) The on-press development type printing plate precursor according to any one of (1) to (5), wherein the arithmetic mean height Sa of the outermost layer surface on the side having the component layer containing the hydroxy acid compound is 0.3 to 20 μm. (7) The on-press development type printing plate precursor according to any one of (1) to (6), wherein the average diameter of micropores on the surface of the anodized coating is 10 to 100 nm, and the lightness L* value in the L*a*b* color system of the surface of the anodized coating on the side of the component layer containing the hydroxy acid compound is 60 to 100. (8) The on-press development type printing plate precursor according to any one of (1) to (7), wherein the micropores in the anodized film are composed of large-diameter pores extending 10 nm to 1,000 nm in a depth direction from the surface of the anodized film, and small-diameter pores that communicate with the bottoms of the large-diameter pores and extend 20 nm to 2,000 nm in a depth direction from the communicating positions, the large-diameter pores having an average diameter of 15 nm to 100 nm at the surface of the anodized film, and the small-diameter pores having an average diameter of 13 nm or less at the communicating positions. (9) The on-press development type printing plate precursor according to any one of (1) to (8), wherein the sagging shape of the edge of the on-press development type printing plate precursor is a sagging amount X of 25 to 150 μm and a sagging width Y of 70 to 300 μm. (10) The on-press development type printing plate precursor according to any one of (1) to (9), which has an image recording layer. (11) The on-press development type printing plate precursor according to (10), wherein the image recording layer contains an infrared absorbing agent, a polymerization initiator, a polymerizable compound, and a polymer compound. (12) The on-press development type printing plate precursor according to (11), wherein the polymer compound is a polymer compound containing a structural unit derived from a styrene compound and / or a structural unit derived from an acrylonitrile compound. (13) The on-press development type printing plate precursor according to (12), wherein in the polymer compound containing a structural unit derived from a styrene compound and a structural unit derived from an acrylonitrile compound, the compositional ratio of the structural unit derived from the styrene compound to the structural unit derived from the acrylonitrile compound is 4:1 to 1:4. (14) The on-press development type printing plate precursor according to any one of (11) to (13), wherein the polymer compound is a polymer particle. (15) The on-press development type printing plate precursor according to (14), wherein the polymer particles are thermoplastic particles. (16) The on-press development type printing plate precursor according to any one of (1) to (15), which has an undercoat layer. (17) The on-press development type printing plate precursor according to any one of (1) to (16), which has a protective layer. (18) The on-press development type printing plate precursor according to (17), wherein the protective layer contains a polyvinyl alcohol resin. (19) The on-press development type printing plate precursor according to any one of (10) to (18), wherein the constituent layer containing the hydroxy acid compound is an image recording layer. (20) The on-press development type printing plate precursor according to any one of (11) to (18), wherein the constituent layer containing the hydroxy acid compound is an undercoat layer. (21) The on-press development type printing plate precursor according to any one of (12) to (18), wherein the constituent layer containing the hydroxy acid compound is a protective layer. (22) The on-press development type printing plate precursor according to any one of (1) to (9), which has a non-photosensitive layer, and all of its constituent layers are non-photosensitive. (23) The on-press development type printing plate precursor according to any one of (1) to (9) and (22), which has an undercoat layer. (24) The on-press development type printing plate precursor according to any one of (1) to (9) and (22) to (23), which has a protective layer. (25) The on-press development type printing plate precursor according to (24), wherein the protective layer contains a polyvinyl alcohol resin. (26) The on-press development type printing plate precursor according to any one of (22) to (25), wherein the constituent layer containing the hydroxy acid compound is a non-photosensitive layer. (27) The on-press development type printing plate precursor according to any one of (23) to (25), wherein the constituent layer containing the hydroxy acid compound is an undercoat layer. (28) The on-press development type printing plate precursor according to (24) or (25), wherein the constituent layer containing the hydroxy acid compound is a protective layer. (29) A method for preparing a printing plate, comprising the steps of: imagewise exposing the on-press development type printing plate precursor described in any one of (10) to (21); and supplying at least one of printing ink and dampening water on a printing press to remove unexposed areas of the image recording layer in the imagewise exposed on-press development type printing plate precursor. (30) A printing method comprising the steps of: supplying at least one of printing ink and dampening water to an on-press development type printing plate precursor described in any one of (22) to (28) on a printing press to remove a non-photosensitive layer in the on-press development type printing plate precursor to prepare a throwaway plate; and carrying out printing using the prepared throwaway plate. Effect of the Invention
[0013] According to the present invention, it is possible to provide an on-press development type printing original plate in which edge contamination is prevented not only after production but also after aging, a method for making a printing plate using an on-press development type printing original plate, and a printing method using an on-press development type printing original plate. Furthermore, according to the present invention, it is possible to provide an on-press development type lithographic printing plate precursor in which deterioration of image formability in edge regions is suppressed. [Brief description of the drawings]
[0014] [Figure 1] 1 is a graph showing an example of an alternating current waveform used in electrochemical graining treatment. [Diagram 2] FIG. 2 is a side view showing an example of a radial cell in electrochemical graining treatment using an alternating current. [Diagram 3] FIG. 2 is a schematic diagram showing the cross-sectional shape of an edge portion of a planographic printing plate precursor. [Figure 4] FIG. 2 is a conceptual diagram illustrating an example of a cutting section of a slitter device. [Diagram 5] FIG. 2 is a side view showing the concept of a brush graining process used in mechanical roughening treatment in the production of an aluminum support. [Figure 6] FIG. 2 is a schematic diagram of an anodizing treatment device used in anodizing treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In the description of groups (atomic groups) in this specification, when there is no indication of substituted or unsubstituted, the term encompasses both unsubstituted and substituted groups. For example, the term "alkyl group" encompasses not only alkyl groups without a substituent (unsubstituted alkyl groups) but also alkyl groups with a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used as a concept including both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl. In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present invention, a combination of two or more preferred embodiments is a more preferred embodiment. In this specification, unless otherwise specified, the mass average molecular weight (Mw) and number average molecular weight (Mn) are molecular weights detected by a gel permeation chromatography (GPC) analyzer using columns of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all product names manufactured by Tosoh Corporation) in a solvent of THF (tetrahydrofuran) and a differential refractometer, and converted using polystyrene as a standard substance. In this specification, the term "printing plate" includes not only lithographic printing plate precursors but also throwaway plate precursors. Furthermore, the term "printing plate" includes not only lithographic printing plates prepared by subjecting a lithographic printing plate precursor to operations such as exposure and development as necessary, but also throwaway plates. In the case of throwaway plate precursors, the operations of exposure and development are not necessarily required. A throwaway plate is a lithographic printing plate that is attached to an unused plate cylinder when, for example, in color newspaper printing, a portion of the page is printed in one color or two colors. A throwaway plate is also called a water plate, a dummy plate, a blank plate, an empty plate, etc. The present invention will be described in detail below.
[0016] [On-press development type printing original plate] The on-press development type printing plate master of the present invention is at least composed of an aluminum support having an anodized film and a constituent layer containing a hydroxy acid compound having two or more hydroxyl groups, and the content of a water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more is substantially the same within the plane of the constituent layer, and the edge of the on-press development type printing plate master has a drooping shape.
[0017] The on-press development type printing plate precursor (hereinafter, sometimes referred to as printing plate precursor) according to the present invention has the above-mentioned configuration, which provides the excellent effect of preventing edge staining not only after production but also after aging. In addition, the on-press development type lithographic printing plate precursor has the excellent effect of suppressing deterioration of image forming properties in edge regions. The on-press development type printing plate precursor according to the present invention will be described in detail below.
[0018] [Aluminum support having an anodized film] An aluminum support having an anodized film which constitutes an on-press development type printing plate precursor will be described.
[0019] The aluminum plate used for the aluminum support is made of a dimensionally stable metal containing aluminum as the main component, i.e., aluminum or an aluminum alloy, and is preferably selected from a pure aluminum plate and an alloy plate containing aluminum as the main component and trace amounts of other elements.
[0020] The foreign elements contained in the aluminum alloy include silicon, iron, manganese, copper, magnesium, chromium, zinc, bismuth, nickel, titanium, etc. The content of foreign elements in the alloy is 10 mass% or less. Pure aluminum plate is preferable, but since completely pure aluminum is difficult to produce due to smelting technology, alloy plate containing a small amount of foreign elements may be used. The composition of the aluminum plate used for the aluminum support is not specified, and conventionally known aluminum plates such as JIS A 1050, JIS A 1100, JIS A 3103, and JIS A 3005 can be appropriately used. The thickness of the aluminum plate is preferably about 0.1 to 0.6 mm.
[0021] (anodic oxide film) The anodized film refers to an anodized aluminum film having extremely fine pores (also called micropores) formed on the surface of an aluminum plate by anodizing. The micropores extend from the surface of the anodized film opposite the aluminum plate in the thickness direction (the aluminum plate side, depth direction). The average diameter (average opening diameter) of the micropores on the surface of the anodized film is preferably 7 nm to 150 nm, more preferably 10 nm to 100 nm, even more preferably 10 nm to 60 nm, particularly preferably 15 nm to 60 nm, and most preferably 18 nm to 40 nm, from the viewpoints of tone reproducibility, printing durability, and printing stain resistance. The depth of the micropores is preferably from 10 nm to 3,000 nm, more preferably from 10 nm to 2,000 nm, and even more preferably from 10 nm to 1,000 nm.
[0022] The shape of the micropores is usually a substantially straight tube shape (substantially cylindrical shape) in which the diameter of the micropores remains almost constant in the depth direction (thickness direction), but they may also be a cone shape in which the diameter decreases continuously in the depth direction (thickness direction), or a shape in which the diameter decreases discontinuously in the depth direction (thickness direction). An example of a micropore having a diameter that discontinuously decreases in the depth direction (thickness direction) is a micropore composed of a large diameter pore portion extending in the depth direction from the surface of the anodized film and a small diameter pore portion that communicates with the bottom of the large diameter pore portion and extends in the depth direction from the communicating position.
[0023] Specifically, micropores composed of large diameter pores extending 10 nm to 1,000 nm in the depth direction from the surface of the anodized film and small diameter pores that communicate with the bottoms of the large diameter pores and extend a further 20 to 2,000 nm in the depth direction from the communicating position are preferred. The large diameter hole portion and the small diameter hole portion will be described in detail below.
[0024] -Large diameter hole- The average diameter (average opening diameter) of the large diameter pores on the surface of the anodized film is preferably 7 nm to 150 nm, more preferably 10 nm to 100 nm, even more preferably 10 nm to 60 nm, particularly preferably 15 nm to 60 nm, and most preferably 18 nm to 40 nm, from the viewpoints of tone reproducibility, printing durability, and printing stain resistance. The average diameter of the large pores is calculated by observing the surface of the anodized film using a field emission scanning electron microscope (FE-SEM) at a magnification of 150,000 times (N=4), measuring the diameter of the micropores (large pores) present in an area of 400 nm x 600 nm in the four obtained images, and calculating the arithmetic mean value of the diameters. If the shape of the large-diameter hole is not circular, the equivalent circle diameter is used. The "equivalent circle diameter" is the diameter of a circle when the shape of the opening is assumed to be a circle having the same projected area as the projected area of the opening.
[0025] The bottoms of the large diameter holes are preferably located at a depth of 70 nm to 1,000 nm (hereinafter also referred to as depth A) from the surface of the anodized film. In other words, the large diameter holes are preferably holes extending 70 nm to 1,000 nm in the depth direction (thickness direction) from the surface of the anodized film. In particular, in terms of superior effects of the manufacturing method for the printing plate precursor, the depth A is more preferably 90 nm to 850 nm, further preferably 90 nm to 800 nm, and particularly preferably 90 nm to 600 nm. The depth is calculated as the arithmetic average value by taking a photograph (150,000 times) of the cross section of the anodized film, measuring the depths of 25 or more large diameter holes, and then calculating the depth.
[0026] The shape of the large diameter hole is not particularly limited, and may be, for example, a substantially straight tube shape (substantially cylindrical) or a cone shape with a diameter decreasing in the depth direction (thickness direction), with a substantially straight tube shape being preferred. The shape of the bottom of the large diameter hole is not particularly limited, and may be a curved (convex) or flat surface. The inner diameter of the large pore is not particularly limited, but is preferably about the same as or smaller than the diameter of the opening. The inner diameter of the large pore may differ from the diameter of the opening by about 1 nm to 10 nm.
[0027] -Small diameter hole- The small diameter hole is a hole that communicates with the bottom of the large diameter hole and extends further in the depth direction (thickness direction) from the communicating position. One small diameter hole usually communicates with one large diameter hole, but two or more small diameter holes may communicate with the bottom of one large diameter hole. The average diameter of the small diameter pores at the communicating positions is preferably 13 nm or less, more preferably 11 nm or less, and particularly preferably 10 nm or less. There is no particular lower limit, but a value of 5 nm is preferable.
[0028] The average diameter of the small pores is calculated by observing the surface of the anodized film with an FE-SEM at a magnification of 150,000 times, taking N=4 images, measuring the diameter of the micropores (small pores) present in the range of 400 nm × 600 nm in the four images obtained, and determining the arithmetic mean value of the diameters. If the large pores are deep, the upper part of the anodized film (the area where the large pores are located) may be cut (for example, cut with argon gas) as necessary, and then the surface of the anodized film may be observed with the FE-SEM to determine the average diameter of the small pores. If the shape of the small diameter hole is not circular, the equivalent circle diameter is used. The "equivalent circle diameter" is the diameter of a circle when the shape of the opening is assumed to be a circle with the same projected area as the projected area of the opening.
[0029] The bottoms of the small diameter holes are preferably located at a position extending 20 nm to 2,000 nm in the depth direction from the communicating position with the large diameter hole (corresponding to the above-mentioned depth A). In other words, the small diameter holes are holes extending in the depth direction (thickness direction) from the communicating position with the large diameter hole, and the depth of the small diameter holes is preferably 20 nm to 2,000 nm, more preferably 100 nm to 1,500 nm, and particularly preferably 200 nm to 1,000 nm. The depth is calculated as the arithmetic average value by taking a photograph (150,000 times) of the cross section of the anodized film, measuring the depths of 25 or more small diameter holes, and then calculating the depth.
[0030] The shape of the small diameter hole is not particularly limited, and may be, for example, a substantially straight tube shape (substantially cylindrical) or a cone shape whose diameter decreases in the depth direction, with a substantially straight tube shape being preferred. The shape of the bottom of the small diameter hole is not particularly limited, and may be a curved (convex) or flat surface. The inner diameter of the small hole is not particularly limited, but may be approximately the same as the diameter at the communicating position, or may be smaller or larger than the above diameter. Note that the inner diameter of the small hole may usually differ from the diameter of the opening by about 1 nm to 10 nm.
[0031] The ratio of the average diameter of the large pores on the surface of the anodized film to the average diameter of the small pores at their connecting positions, i.e., (average diameter of the large pores on the surface of the anodized film) / (average diameter of the small pores at their connecting positions), is preferably 1.1 to 13, and more preferably 2.5 to 6.5. The ratio of the depth of the large diameter hole portions to the depth of the small diameter hole portions, (depth of the large diameter hole portions) / (depth of the small diameter hole portions), is preferably 0.005-50, and more preferably 0.025-40.
[0032] In an on-press development type lithographic printing plate precursor, from the viewpoint of improving image visibility, it is useful that the anodized film surface of the aluminum support (the surface on which the image recording layer is formed) has high brightness. In the printing process of a lithographic printing plate, a plate inspection is usually performed to check whether the intended image has been recorded before the printing plate is mounted on a printing press. In the case of an on-press development type lithographic printing plate precursor, it is required to check the image at the stage where the image is exposed, so a means for generating a so-called print-out image in the image-exposed area is applied. A method for quantitatively evaluating the visibility (image visibility) of the image area of an image-exposed on-press development type lithographic printing plate precursor can be to measure the lightness of the image-exposed area and the lightness of the unexposed area and determine the difference between them. Here, the lightness can be the lightness L* value in the CIEL*a*b* color system, and the measurement can be performed using a colorimeter (SpectroEye, manufactured by X-Rite Corporation). The greater the difference between the lightness of the image-exposed area and the lightness of the unexposed area obtained by measurement, the easier the image area is to see. It has been found that in order to increase the difference in brightness between the image-exposed and unexposed areas, it is effective to increase the brightness L* value in the CIEL*a*b* color system of the anodized film surface. In other words, the brightness L* value is preferably 60 to 100.
[0033] If necessary, the aluminum support having an anodized coating may have a backcoat layer containing an organic polymer compound described in JP-A-5-45885 or a silicon alkoxy compound described in JP-A-6-35174 on the side opposite to the side on which the constituent layer containing a hydroxy acid compound having two or more hydroxyl groups is formed.
[0034] (Production of aluminum substrate having anodized film) The aluminum support having an anodized film can be manufactured by a known method. The manufacturing method of the aluminum support having an anodized film is not particularly limited. A preferred embodiment of the manufacturing method of the aluminum support having an anodized film includes a step of roughening an aluminum plate (roughening treatment step), a step of anodizing the roughened aluminum plate (anodizing treatment step), and a step of contacting the aluminum plate having an anodized film obtained in the anodizing treatment step with an acid aqueous solution or an alkali aqueous solution to expand the diameter of the micropores in the anodized film (pore widening treatment step).
[0035] Each step will be described in detail below.
[0036] <Surface roughening process> The surface roughening step is a step of performing a surface roughening treatment, including an electrochemical surface roughening treatment, on the surface of the aluminum plate. The surface roughening step is preferably performed before the anodizing step described below, but may not be performed if the surface of the aluminum plate already has a desired surface shape.
[0037] The surface roughening treatment may be performed by electrochemical surface roughening alone, or may be performed by combining electrochemical surface roughening treatment with at least one of mechanical surface roughening treatment and chemical surface roughening treatment. When mechanical graining and electrochemical graining are combined, it is preferable to carry out the electrochemical graining after the mechanical graining.
[0038] The electrochemical graining treatment is preferably carried out in an aqueous solution of nitric acid or hydrochloric acid.
[0039] Mechanical graining is generally performed for the purpose of making the surface of an aluminum plate have a surface roughness Ra of 0.35 to 1.0 μm. The conditions for the mechanical graining treatment are not particularly limited, but the treatment can be carried out, for example, according to the method described in JP-B-50-40047. The mechanical graining treatment can be carried out by a brush graining treatment using a pumice suspension or by a transfer method. The chemical graining treatment is not particularly limited, and can be carried out according to a known method.
[0040] After the mechanical roughening treatment, it is preferable to carry out the following chemical etching treatment. The chemical etching treatment carried out after the mechanical graining treatment is carried out to smooth the uneven edges of the surface of the aluminum plate, prevent the ink from catching during printing, improve the stain resistance of the lithographic printing plate, and remove unwanted material such as abrasive particles remaining on the surface. Known chemical etching processes include acid etching and alkali etching, but a method that is particularly excellent in terms of etching efficiency is chemical etching using an alkaline solution (hereinafter also referred to as "alkaline etching process").
[0041] The alkaline agent used in the alkaline solution is not particularly limited, but suitable examples include caustic soda, caustic potash, sodium metasilicate, sodium carbonate, sodium aluminate, and sodium gluconate. The alkaline solution may contain aluminum ions. The concentration of the alkaline agent in the alkaline solution is preferably 0.01% by mass or more, more preferably 3% by mass or more, and is preferably 30% by mass or less, more preferably 25% by mass or less. Furthermore, the temperature of the alkaline solution is preferably room temperature or higher, more preferably 30° C. or higher, and is preferably 80° C. or lower, more preferably 75° C. or lower.
[0042] The etching amount is 0.01 g / m 2 More than 0.05 g / m is preferable. 2 More preferably, 30 g / m 2 Less than 20 g / m is preferable. 2 The following is more preferred: The treatment time is preferably 2 seconds to 5 minutes depending on the amount of etching, and more preferably 2 to 10 seconds from the viewpoint of improving productivity.
[0043] When alkaline etching treatment is performed after mechanical roughening treatment, it is preferable to perform a chemical etching treatment (hereinafter also referred to as "desmutting treatment") using a low-temperature acidic solution in order to remove products produced by the alkaline etching treatment. The acid used in the acidic solution is not particularly limited, but examples thereof include sulfuric acid, nitric acid, and hydrochloric acid. The concentration of the acidic solution is preferably 1 to 50% by mass. The temperature of the acidic solution is preferably 20 to 80° C. When the concentration and temperature of the acidic solution are within these ranges, the resistance to dot-like staining in a lithographic printing plate using an aluminum support is further improved.
[0044] A preferred embodiment of the surface roughening treatment step will be exemplified below. -Aspect SA- The process shown in (1) to (8) is carried out in this order. (1) Chemical etching treatment using an alkaline aqueous solution (first alkaline etching treatment) (2) Chemical etching treatment using an acidic aqueous solution (first desmutting treatment) (3) Electrochemical roughening treatment using an aqueous solution mainly containing nitric acid (first electrochemical roughening treatment) (4) Chemical etching treatment using an alkaline aqueous solution (second alkaline etching treatment) (5) Chemical etching treatment using an acidic aqueous solution (second desmutting treatment) (6) Electrochemical roughening treatment using an aqueous solution mainly containing hydrochloric acid (second electrochemical roughening treatment) (7) Chemical etching treatment using an alkaline aqueous solution (third alkaline etching treatment) (8) Chemical etching treatment using an acidic aqueous solution (third desmutting treatment)
[0045] -SB- The process shown in (11) to (15) is carried out in this order. (11) Chemical etching treatment using an alkaline aqueous solution (fourth alkaline etching treatment) (12) Chemical etching treatment using an acidic aqueous solution (fourth desmutting treatment) (13) Electrochemical roughening treatment using an aqueous solution mainly containing hydrochloric acid (third electrochemical roughening treatment) (14) Chemical etching treatment using an alkaline aqueous solution (fifth alkaline etching treatment) (15) Chemical etching treatment using an acidic aqueous solution (5th desmutting treatment)
[0046] Before the treatment (1) of the above-mentioned embodiment SA or before the treatment (11) of the embodiment SB, a mechanical graining treatment may be carried out, if necessary.
[0047] The amount of aluminum plate dissolved in the first and fourth alkaline etching treatments was 0.5 g / m 2 ~30g / m 2 is preferred, and 1.0 g / m 2 ~20g / m 2 is more preferred.
[0048] The aqueous solution mainly containing nitric acid for use in the first electrochemical graining treatment in embodiment SA may be an aqueous solution for use in electrochemical graining treatment using direct or alternating current, such as an aqueous solution obtained by adding aluminum nitrate, sodium nitrate, ammonium nitrate, or the like to a 1 g / L to 100 g / L aqueous solution of nitric acid. The aqueous solution mainly containing hydrochloric acid used in the second electrochemical graining treatment in embodiment SA and the third electrochemical graining treatment in embodiment SB includes an aqueous solution used in electrochemical graining treatment using direct or alternating current. For example, an aqueous solution obtained by adding 0 g / L to 30 g / L of sulfuric acid to an aqueous solution of 1 g / L to 100 g / L of hydrochloric acid may be included. Note that this aqueous solution may further include nitrate ions such as aluminum nitrate, sodium nitrate, or ammonium nitrate; or chloride ions such as aluminum chloride, sodium chloride, or ammonium chloride.
[0049] The AC power waveform for the electrochemical graining treatment may be a sine wave, a square wave, a trapezoidal wave, a triangular wave, etc. The frequency is preferably 0.1 Hz to 250 Hz. FIG. 1 is a graph showing an example of an alternating current waveform used in electrochemical surface roughening treatment. In FIG. 1, ta is the anode reaction time, tc is the cathode reaction time, tp is the time from 0 to the peak current, Ia is the current at the peak on the anode cycle side, and Ic is the current at the peak on the cathode cycle side. In the trapezoidal wave, the time tp from 0 to the peak current is preferably 1 msec to 10 msec. The conditions for one cycle of AC used in the electrochemical graining treatment are preferably such that the ratio tc / ta of the anode reaction time ta to the cathode reaction time tc of the aluminum plate is 1 to 20, the ratio Qc / Qa of the quantity of electricity Qc when the aluminum plate is the anode to the quantity of electricity Qa when the aluminum plate is the anode is 0.3 to 20, and the anode reaction time ta is in the range of 5 msec to 1,000 msec. The current density is the peak value of the trapezoidal wave, and both the anode cycle side Ia and the cathode cycle side Ic of the current are 10 to 200 A / dm 2The ratio Ic / Ia is preferably 0.3 to 20. The total amount of electricity involved in the anodic reaction of the aluminum plate at the time when the electrochemical graining treatment is completed is 25 C / dm 2 ~1,000C / dm 2 is preferred.
[0050] For electrochemical roughening treatment using alternating current, the device shown in FIG. 2 can be used. FIG. 2 is a side view showing an example of a radial cell for electrochemical surface roughening treatment using an alternating current. 2, 50 is a main electrolytic cell, 51 is an AC power source, 52 is a radial drum roller, 53a and 53b are main electrodes, 54 is an electrolyte supply port, 55 is an electrolyte, 56 is a slit, 57 is an electrolyte passage, 58 is an auxiliary anode, 60 is an auxiliary anode cell, and W is an aluminum plate. When two or more electrolytic cells are used, the electrolysis conditions may be the same or different. The aluminum sheet W is wound around a radial drum roller 52 immersed in a main electrolytic cell 50, and is electrolyzed by main electrodes 53a and 53b connected to an AC power source 51 during transportation. An electrolyte 55 is supplied from an electrolyte supply port 54 through a slit 56 to an electrolyte passage 57 between the radial drum roller 52 and the main electrodes 53a and 53b. The aluminum sheet W treated in the main electrolytic cell 50 is then electrolyzed in an auxiliary anode cell 60. In this auxiliary anode cell 60, an auxiliary anode 58 is disposed opposite the aluminum sheet W, and the electrolyte 55 is supplied so as to flow through the space between the auxiliary anode 58 and the aluminum sheet W.
[0051] The amount of aluminum plate dissolved in the second alkaline etching treatment is set to 1.0 g / m2 in order to facilitate the production of a desired printing plate master. 2 ~20g / m 2 is preferred, and 2.0 g / m 2 ~10g / m 2 is more preferred.
[0052] The amount of dissolution of the aluminum plate in the third alkaline etching treatment and the fifth alkaline etching treatment is set to 0.01 g / m so as to facilitate the production of a predetermined printing plate blank. 2~0.8g / m 2 is preferred, and 0.05 g / m 2 ~0.3g / m 2 is more preferred.
[0053] In the chemical etching treatments (first to fifth desmutting treatments) using an acidic aqueous solution, an acidic aqueous solution containing phosphoric acid, nitric acid, sulfuric acid, chromic acid, hydrochloric acid, or a mixed acid containing two or more of these acids is suitably used. The concentration of the acid in the acidic aqueous solution is preferably 0.5% by mass to 60% by mass.
[0054] <Anodizing process> The anodizing process is a process for forming an aluminum oxide film on the surface of the aluminum plate by anodizing the aluminum plate that has been subjected to the surface roughening process. The anodizing process forms an aluminum anodized film having micropores on the surface of the aluminum plate. The anodizing treatment can be carried out according to a method conventionally known in this field by appropriately setting the production conditions taking into consideration the desired shape of the micropores, etc.
[0055] In the anodizing process, an aqueous solution of sulfuric acid, phosphoric acid, oxalic acid, or the like can be mainly used as the electrolyte. In some cases, an aqueous or non-aqueous solution of chromic acid, sulfamic acid, benzenesulfonic acid, or the like, or a combination of two or more of these, can also be used. When a direct or alternating current is passed through the aluminum plate in the electrolyte, an anodized film can be formed on the surface of the aluminum plate. The electrolyte may contain aluminum ions. The content of aluminum ions is not particularly limited, but is preferably 1 to 10 g / L.
[0056] The conditions for the anodizing treatment are appropriately set depending on the electrolyte used, but generally, the electrolyte concentration is 1 to 80 mass % (preferably 5 to 20 mass %), the solution temperature is 5 to 70°C (preferably 10 to 60°C), and the current density is 0.5 to 60 A / dm 2 (Preferably 5 to 50 A / dm 2), a voltage of 1 to 100 V (preferably 5 to 50 V), and an electrolysis time of 1 to 100 seconds (preferably 5 to 60 seconds) are appropriate.
[0057] A preferred example of the anodizing treatment is the method described in British Patent No. 1,412,768, in which anodizing is carried out in sulfuric acid at a high current density.
[0058] Anodizing treatment can be performed multiple times. One or more of the conditions such as the type, concentration, temperature, current density, voltage, and electrolysis time of the electrolyte used in each anodizing treatment can be changed. When the number of anodizing treatments is two, the first anodizing treatment is sometimes called the first anodizing treatment, and the second anodizing treatment is sometimes called the second anodizing treatment. By performing the first anodizing treatment and the second anodizing treatment, anodizing films having different shapes can be formed, making it possible to provide a printing plate master with excellent printing performance. Furthermore, it is also possible to carry out the pore widening treatment described below following the anodizing treatment, and then carry out the anodizing treatment again. In this case, the first anodizing treatment, the pore widening treatment, and the second anodizing treatment are carried out. By utilizing the method of performing the above-mentioned first anodizing treatment, pore widening treatment, and second anodizing treatment, it is possible to form micropores consisting of large diameter pores extending in the depth direction from the surface of the anodized film described above and small diameter pores that communicate with the bottom of the large diameter pores and extend in the depth direction from the communicating position.
[0059] <Pore widening process> The pore widening treatment step is a treatment (pore diameter enlargement treatment) for enlarging the diameter of the micropores present in the anodized film formed by the anodized film treatment step described above. This pore widening treatment enlarges the diameter of the micropores, forming an anodized film having micropores with a larger average diameter.
[0060] The pore widening treatment can be carried out by contacting the aluminum plate obtained by the above-mentioned anodizing treatment step with an acid aqueous solution or an alkaline aqueous solution. The contacting method is not particularly limited, and examples thereof include an immersion method and a spray method. Among these, the immersion method is preferred.
[0061] When an alkaline aqueous solution is used in the pore widening treatment step, it is preferable to use at least one alkaline aqueous solution selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide. The concentration of the alkaline aqueous solution is preferably 0.1 to 5 mass%. It is appropriate to adjust the pH of the alkaline aqueous solution to 11 to 13, and contact the aluminum sheet with the alkaline aqueous solution for 1 to 300 seconds (preferably 1 to 50 seconds) under conditions of 10 to 70°C (preferably 20 to 50°C). In this case, the alkaline treatment liquid may contain metal salts of polyvalent weak acids such as carbonates, borates, and phosphates.
[0062] When an aqueous acid solution is used in the pore widening treatment step, it is preferable to use an aqueous solution of an inorganic acid such as sulfuric acid, phosphoric acid, nitric acid, or hydrochloric acid, or a mixture thereof. The concentration of the aqueous acid solution is preferably 1 to 80% by mass, more preferably 5 to 50% by mass. It is appropriate to contact the aluminum sheet with the aqueous acid solution for 1 to 300 seconds (preferably 1 to 150 seconds) under conditions of a liquid temperature of the aqueous acid solution of 5 to 70°C (preferably 10 to 60°C). The alkaline or acidic aqueous solution may contain aluminum ions. The content of aluminum ions is not particularly limited, but is preferably 1 to 10 g / L.
[0063] The method for producing an aluminum support having an anodized film may include a hydrophilization treatment step in which a hydrophilization treatment is carried out after the pore widening treatment step. For the hydrophilization treatment, a known method described in paragraphs 0109 to 0114 of JP-A-2005-254638 can be used.
[0064] The hydrophilization treatment is preferably carried out by a method of immersing the substrate in an aqueous solution of an alkali metal silicate such as sodium silicate or potassium silicate, or by a method of coating a hydrophilic vinyl polymer or a hydrophilic compound to form a hydrophilic undercoat layer.
[0065] The hydrophilization treatment with an aqueous solution of an alkali metal silicate such as sodium silicate or potassium silicate can be carried out according to the method and procedure described in US Pat. Nos. 2,714,066 and 3,181,461.
[0066] [Constituent layer containing hydroxy acid compound having two or more hydroxyl groups] A constituent layer that constitutes an on-press development type printing plate precursor and that contains a hydroxy acid compound having two or more hydroxyl groups (hereinafter also referred to as a "specific constituent layer") will be described. The specific component layer contains a hydroxy acid compound having two or more hydroxyl groups.
[0067] (Hydroxy acid compounds having two or more hydroxyl groups) The specific component layer contains a hydroxy acid compound having two or more hydroxyl groups (hereinafter, also referred to as a "specific hydroxy acid compound").
[0068] The specific hydroxy acid compound includes a hydroxycarboxylic acid having two or more hydroxyl groups and a salt thereof, such as a sodium salt, a potassium salt, a lithium salt, a calcium salt, a magnesium salt, an aluminum salt, or an ammonium salt. The number of hydroxyl groups in the hydroxycarboxylic acid having two or more hydroxyl groups is preferably 2 to 15, more preferably 3 to 10, and further preferably 4 to 7. The number of carboxy groups in the hydroxycarboxylic acid having two or more hydroxyl groups is preferably 1-10, more preferably 1-5, and even more preferably 1 to 3.
[0069] From the viewpoint of preventing edge stains, it is preferable that the specific hydroxy acid compound has high hydrophilicity. The hydrophilicity of the specific hydroxy acid compound can be expressed by the ClogP value, which is generally known as an index of the hydrophilicity of a compound. The ClogP value of the specific hydroxy acid compound is preferably 0.5 or less, more preferably -1 or less, and even more preferably -3 or less. In addition, from the viewpoint of image forming properties in the edge region, the ClogP value of the specific hydroxy acid compound is preferably -10 or more, more preferably -7 or more, and even more preferably -5 or more. Here, the ClogP value of the specific hydroxy acid compound is a value calculated from the molecular structure using the molecular structure editor software "ChemDraw Professional 2016."
[0070] The molecular weight of the specific hydroxy acid compound is preferably 1,000 or less. By having a molecular weight of 1,000 or less, the specific hydroxy acid compound can easily migrate to the surface of the anodized film during on-machine development, and can effectively contribute to preventing edge stains. The molecular weight of the specific hydroxy acid compound is more preferably 80 to 1,000, further preferably 100 to 500, and further more preferably 100 to 300.
[0071] Examples of the specific hydroxy acid compound include glyceric acid, gluconic acid, tartaric acid, mevalonic acid, pantoic acid, quinic acid, shikimic acid, gallic acid, caffeic acid, 2,3-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid, 2,5-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, 2,3,4-trihydroxybenzoic acid, 3,4,5-trihydroxybenzoic acid, sodium gluconate, potassium gluconate, sodium tartrate, and sodium gallate. As the specific hydroxy acid compound, gluconic acid, tartaric acid, mevalonic acid, quinic acid, sodium gluconate, potassium gluconate, sodium tartrate, etc. are preferred.
[0072] The specific hydroxy acid compound may be used alone or in combination of two or more kinds.
[0073] The content of the specific hydroxy acid compound in the specific component layer is 10 to 300 mg / m from the viewpoint of image forming properties in the edge region. 2 is preferable, and 30 to 200 mg / m 2 More preferably, 50 to 100 mg / m 2 is more preferred. The content of the specific hydroxy acid compound is substantially the same in the plane of the specific component layer. Here, "the content of the specific hydroxy acid compound is substantially the same in the plane of the specific component layer" means that the specific hydroxy acid compound is almost uniformly present in the plane of the specific component layer, and there is no substantial difference in the content of the specific hydroxy acid compound between the center and the end of the on-press development type printing plate precursor. That is, it means that there is no content difference other than the content difference of the specific hydroxy acid compound in the plane of the specific component layer that may normally occur when the specific component layer is applied. Therefore, the present invention differs from intentionally applying a specific hydroxy acid compound only to the edges of an on-press development type printing plate precursor, thereby creating a state in which the content of the specific hydroxy acid compound at the edges is greater than the content of the specific hydroxy acid compound in areas other than the edges.
[0074] In the plane of the specific component layer, the content of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20 ° C is substantially the same. Here, "the content of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20 ° C is substantially the same in the plane of the specific component layer" means that the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20 ° C is almost uniformly present in the plane of the specific component layer, and there is no substantial difference in the content of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20 ° C at the center and end parts of the on-press development type printing plate precursor. That is, it means that there is no content difference other than the content difference of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20 ° C in the plane of the specific component layer that can usually occur when the specific component layer is applied. Therefore, the present invention differs from intentionally applying a water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more only to the edges of an on-press development type printing plate master, thereby creating a state in which the content of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more at the edges is greater than the content of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water at 20°C of 10 g / L or more in areas other than the edges.
[0075] Preferred examples of the water-soluble compound having a molecular weight of 60 to 300 and a solubility in water of 10 g / L or more at 20° C. include polyols, betaines, organic sulfonates, organic sulfates, organic carboxylic acids or salts thereof, and amino acids. Specific examples of these are described in paragraphs 0022 to 0027 of WO2016 / 053443.
[0076] The specific component layer is a component layer that contains a specific hydroxy acid compound. Therefore, when a component layer of an on-press development type lithographic printing plate precursor and a disposable plate precursor, such as an image recording layer, an undercoat layer, a protective layer or a non-photosensitive layer, contains a specific hydroxy acid compound, the component layer corresponds to a specific component layer.
[0077] [On-press development type lithographic printing plate original plate] Hereinafter, an on-press development type lithographic printing plate precursor (hereinafter also referred to as "lithographic printing plate precursor"), which is one embodiment of the on-press development type printing plate precursor according to the present invention, will be described. The lithographic printing plate precursor has an image recording layer on the aluminum support having the above-mentioned anodized film.
[0078] [Image Recording Layer] According to one preferred embodiment of the image recording layer in the lithographic printing plate precursor, the image recording layer contains an infrared absorbing agent, a polymerization initiator, a polymerizable compound, and a polymer compound. The image recording layer preferably further contains a chain transfer agent. According to another preferred embodiment of the image recording layer, the image recording layer contains an infrared absorbing agent, heat-fusible particles, and a binder polymer.
[0079] (Infrared absorber) The infrared absorbing agent has a function of being excited by infrared rays and transferring electrons and / or energy to a polymerization initiator, etc. Also, it has a function of converting the absorbed infrared rays into heat. The infrared absorbing agent preferably has a maximum absorption in the wavelength range of 750 to 1,400 nm. Examples of the infrared absorbing agent include dyes and pigments, and dyes are preferably used.
[0080] As the dye, commercially available dyes and known dyes described in documents such as "Dye Handbook" (edited by the Organic Synthesis Chemistry Association, published in 1970) can be used. Specific examples of the dye include azo dyes, metal complex azo dyes, pyrazolone azo dyes, naphthoquinone dyes, anthraquinone dyes, phthalocyanine dyes, carbonium dyes, quinoneimine dyes, methine dyes, cyanine dyes, squarylium dyes, pyrylium salts, and metal thiolate complex dyes. Of the dyes, cyanine dyes, squarylium dyes and pyrylium salts are preferred, cyanine dyes are more preferred, and indolenine cyanine dyes are particularly preferred.
[0081] The cyanine dye includes a cyanine dye represented by the following formula (a).
[0082] [ka]
[0083] In formula (a), X 1 is a hydrogen atom, a halogen atom, -N(R 9 )(R 10 ), -X 2 -L 1 or the group shown below, where R 9 and R 10 may be the same or different, and each independently represents an aromatic hydrocarbon group having 6 to 10 carbon atoms, an alkyl group having 1 to 8 carbon atoms, or a hydrogen atom, or R 9 and R 10and may be bonded to each other to form a ring. The aromatic hydrocarbon group having 6 to 10 carbon atoms or the alkyl group having 1 to 8 carbon atoms may have a substituent. R 9 and R 10 Preferably, X is a phenyl group. 2 represents an oxygen atom or a sulfur atom, L 1 represents a hydrocarbon group having 1 to 12 carbon atoms or a hydrocarbon group having 1 to 12 carbon atoms containing a hetero atom. Here, the hetero atom represents N, S, O, a halogen atom, or Se. In the groups shown below, Xa - is Za - and Ra represents a hydrogen atom or a substituent selected from an alkyl group, an aryl group, a substituted or unsubstituted amino group, and a halogen atom.
[0084] [ka]
[0085] In formula (a), R 1 and R 2 Each independently represents a hydrocarbon group having 1 to 12 carbon atoms. In view of the storage stability of the coating solution for the image recording layer, R 1 and R 2 is preferably a hydrocarbon group having 2 or more carbon atoms, and R 1 and R 2 are particularly preferably bonded to each other to form a 5- or 6-membered ring.
[0086] In formula (a), Ar 1 and Ar 2 may be the same or different, and each represents an aromatic hydrocarbon group. The aromatic hydrocarbon group may have a substituent. Preferred aromatic hydrocarbon groups include a benzene ring group and a naphthalene ring group. Preferred substituents include a hydrocarbon group having 12 or less carbon atoms, a halogen atom, and an alkoxy group having 12 or less carbon atoms. Y 1 and Y 2 may be the same or different, and each represents a sulfur atom or a dialkylmethylene group having 12 or less carbon atoms. 3 and R 4may be the same or different, and each represents a hydrocarbon group having 20 or less carbon atoms. The hydrocarbon group having 20 or less carbon atoms may have a substituent. Preferred substituents include an alkoxy group, a carboxy group, and a sulfo group having 12 or less carbon atoms. R 5 , R 6 , R 7 and R 8 may be the same or different, and each represents a hydrogen atom or a hydrocarbon group having 12 or less carbon atoms. In view of the ease of availability of raw materials, a hydrogen atom is preferred. - represents a counter anion. However, when the cyanine dye represented by formula (a) has an anionic substituent in its structure and does not need to be neutralized by the charge, Za - is not necessary. - From the viewpoint of storage stability of the image recording layer coating solution, a halide ion, a perchlorate ion, a tetrafluoroborate ion, a hexafluorophosphate ion, or a sulfonate ion is preferred, and a perchlorate ion, a hexafluorophosphate ion, or an arylsulfonate ion is more preferred.
[0087] In the cyanine dye represented by formula (a), X 1 More preferably, X is a diphenylamino group. 1 is a diphenylamino group, and Y 1 and Y 2 It is more preferable that both of are dimethylmethylene groups.
[0088] Specific examples of cyanine dyes include the compounds described in paragraphs 0017 to 0019 of JP-A-2001-133969, the compounds described in paragraphs 0016 to 0021 of JP-A-2002-023360, and the compounds described in paragraphs 0012 to 0037 of JP-A-2002-040638, preferably the compounds described in paragraphs 0034 to 0041 of JP-A-2002-278057, and paragraphs 0080 to 0086 of JP-A-2008-195018, and particularly preferably the compounds described in paragraphs 0035 to 0043 of JP-A-2007-90850. In addition, the compounds described in paragraphs 0008 to 0009 of JP-A No. 5-5005 and paragraphs 0022 to 0025 of JP-A No. 2001-222101 can also be preferably used. As the pigment, the compounds described in paragraphs 0072 to 0076 of JP-A No. 2008-195018 are preferred.
[0089] The infrared absorbing agent may be used alone or in combination of two or more kinds. The content of the infrared absorbing agent is preferably from 0.05 to 30% by mass, more preferably from 0.1 to 20% by mass, and even more preferably from 0.2 to 10% by mass, based on the total solid content of the image recording layer.
[0090] (Polymerization initiator) The polymerization initiator is a compound that generates polymerization initiating species such as radicals or cations by the energy of light, heat, or both, and can be appropriately selected from known thermal polymerization initiators, compounds having bonds with small bond dissociation energy, photopolymerization initiators, etc. The polymerization initiator is preferably an infrared-sensitive polymerization initiator. The polymerization initiator is preferably a radical polymerization initiator. Two or more radical polymerization initiators may be used in combination.
[0091] The radical polymerization initiator may be either an electron-accepting polymerization initiator or an electron-donating polymerization initiator.
[0092] <Electron-accepting polymerization initiator> Examples of the electron-accepting polymerization initiator include organic halides, carbonyl compounds, azo compounds, organic peroxides, metallocene compounds, azide compounds, hexaarylbiimidazole compounds, disulfone compounds, oxime ester compounds, and onium salt compounds.
[0093] As the organic halide, for example, the compounds described in paragraphs 0022 to 0023 of JP-A No. 2008-195018 are preferable. As the carbonyl compound, for example, the compound described in paragraph 0024 of JP-A-2008-195018 is preferable. Examples of the azo compound include the azo compounds described in JP-A-8-108621. As the organic peroxide, for example, the compound described in paragraph 0025 of JP-A-2008-195018 is preferable. As the metallocene compound, for example, the compound described in paragraph 0026 of JP-A-2008-195018 is preferable. Examples of the azide compound include compounds such as 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone. As the hexaarylbiimidazole compound, for example, the compound described in paragraph 0027 of JP-A-2008-195018 is preferable. Examples of the disulfone compound include the compounds described in JP-A-61-166544 and JP-A-2002-328465. As the oxime ester compound, for example, the compounds described in paragraphs 0028 to 0030 of JP-A No. 2008-195018 are preferable.
[0094] Among the electron-accepting polymerization initiators, onium salts such as iodonium salts, sulfonium salts, and azinium salts are more preferred. Iodonium salts and sulfonium salts are particularly preferred. Specific examples of iodonium salts and sulfonium salts are shown below, but the present invention is not limited thereto.
[0095] Preferred examples of iodonium salts include diphenyliodonium salts, particularly diphenyliodonium salts having an electron-donating group as a substituent, for example, diphenyliodonium salts substituted with an alkyl group or an alkoxyl group, and asymmetric diphenyliodonium salts are also preferred. Specific examples include diphenyliodonium hexafluorophosphate, 4-methoxyphenyl-4-(2-methylpropyl)phenyliodonium hexafluorophosphate, 4-(2-methylpropyl)phenyl-p-tolyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, 4-hexyloxyphenyl-2,4-diethoxyphenyliodonium tetrafluoroborate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium 1-perfluorobutanesulfonate, 4-octyloxyphenyl-2,4,6-trimethoxyphenyliodonium hexafluorophosphate, and bis(4-t-butylphenyl)iodonium hexafluorophosphate.
[0096] Examples of sulfonium salts include triarylsulfonium salts, particularly triarylsulfonium salts having an electron-withdrawing group as a substituent, for example, triarylsulfonium salts in which at least a part of the groups on the aromatic ring are substituted with halogen atoms, and more preferably triarylsulfonium salts in which the total number of halogen atoms substituted on the aromatic ring is 4 or more. Specific examples include triphenylsulfonium hexafluorophosphate, triphenylsulfonium benzoylformate, bis(4-chlorophenyl)phenylsulfonium benzoylformate, bis(4-chlorophenyl)-4-methylphenylsulfonium tetrafluoroborate, tris(4-chlorophenyl)sulfonium 3,5-bis(methoxycarbonyl)benzenesulfonate, tris(4-chlorophenyl)sulfonium hexafluorophosphate, and tris(2,4-dichlorophenyl)sulfonium hexafluorophosphate.
[0097] The electron-accepting polymerization initiator may be used alone or in combination of two or more kinds. The content of the electron-accepting polymerization initiator is preferably from 0.1 to 50% by mass, more preferably from 0.5 to 30% by mass, and even more preferably from 0.8 to 20% by mass, based on the total solid content of the image recording layer.
[0098] <Electron-donating polymerization initiator> The electron-donating polymerization initiator contributes to improving the printing durability of the lithographic printing plate produced from the lithographic printing plate precursor. The electron-donating polymerization initiator may be of the following five types: (i) Alkyl or aryl ate complex: It is believed that the carbon-hetero bond is oxidatively cleaved to generate an active radical. Specifically, borate compounds and the like are included. (ii) Aminoacetic acid compound: It is believed that the CX bond on the carbon adjacent to the nitrogen is cleaved by oxidation to generate an active radical. X is preferably a hydrogen atom, a carboxy group, a trimethylsilyl group, or a benzyl group. Specifically, N-phenylglycines (which may have a substituent on the phenyl group) and N-phenyliminodiacetic acid (which may have a substituent on the phenyl group) are included. (iii) Sulfur-containing compound: A compound in which the nitrogen atom of the aminoacetic acid compound described above is replaced with a sulfur atom can generate an active radical by the same action. Specifically, phenylthioacetic acid (which may have a substituent on the phenyl group) and the like are included. (iv) Tin-containing compounds: Compounds in which the nitrogen atom of the aminoacetic acid compound described above is replaced with a tin atom can generate active radicals by the same action. (v) Sulfinates: Can generate active radicals by oxidation. Specific examples include sodium arylsulfinates.
[0099] Among the electron donating polymerization initiators, borate compounds are preferred. As the borate compound, tetraarylborate compounds or monoalkyltriarylborate compounds are preferred, and from the viewpoint of compound stability, tetraarylborate compounds are more preferred. The counter cation of the borate compound is preferably an alkali metal ion or a tetraalkylammonium ion, and more preferably a sodium ion, a potassium ion or a tetrabutylammonium ion.
[0100] Specific examples of the borate compound include the following compounds. c + represents a monovalent cation, preferably an alkali metal ion or a tetraalkylammonium ion, more preferably an alkali metal ion or a tetrabutylammonium ion, and Bu represents an n-butyl group.
[0101] [ka]
[0102] [ka]
[0103] [ka]
[0104] [ka]
[0105] The electron-donating polymerization initiator may be used alone or in combination of two or more kinds. The content of the electron-donating polymerization initiator is preferably from 0.01 to 30% by mass, more preferably from 0.05 to 25% by mass, and even more preferably from 0.1 to 20% by mass, based on the total solid content of the image recording layer.
[0106] (polymerizable compound) The polymerizable compound may be, for example, a radical polymerizable compound or a cationic polymerizable compound, but is preferably an addition polymerizable compound (ethylenically unsaturated compound) having at least one ethylenically unsaturated bond. As the ethylenically unsaturated compound, a compound having at least one terminal ethylenically unsaturated bond is preferred, and a compound having two or more terminal ethylenically unsaturated bonds is more preferred. The polymerizable compound may have a chemical form such as, for example, a monomer, a prepolymer, i.e., a dimer, a trimer, or an oligomer, or a mixture thereof.
[0107] Examples of the monomer include unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, itaconic acid, crotonic acid, isocrotonic acid, maleic acid), their esters, and amides. Preferably, esters of unsaturated carboxylic acids and polyhydric alcohol compounds, and amides of unsaturated carboxylic acids and polyvalent amine compounds are used. In addition, addition reaction products of unsaturated carboxylic acid esters or amides having nucleophilic substituents such as hydroxyl groups, amino groups, and mercapto groups with monofunctional or polyfunctional isocyanates or epoxy groups, and dehydration condensation reaction products of monofunctional or polyfunctional carboxylic acids are also preferably used. In addition, addition reaction products of unsaturated carboxylic acid esters or amides having electrophilic substituents such as isocyanate groups and epoxy groups with monofunctional or polyfunctional alcohols, amines, and thiols, and substitution reaction products of unsaturated carboxylic acid esters or amides having eliminable substituents such as halogen atoms and tosyloxy groups with monofunctional or polyfunctional alcohols, amines, and thiols are also suitable. As another example, compounds in which the above unsaturated carboxylic acids are replaced with unsaturated phosphonic acids, styrene, vinyl ethers, etc. can also be used. These compounds are described in JP-T-2006-508380, JP-A-2002-287344, JP-A-2008-256850, JP-A-2001-342222, JP-A-9-179296, JP-A-9-179297, JP-A-9-179298, JP-A-2004-294935, JP-A-2006-243493, JP-A-2002-275129, JP-A-2003-64130, JP-A-2003-280187, JP-A-10-333321, and the like.
[0108] Specific examples of monomers of esters of polyhydric alcohol compounds and unsaturated carboxylic acids include acrylic esters such as ethylene glycol diacrylate, 1,3-butanediol diacrylate, tetramethylene glycol diacrylate, propylene glycol diacrylate, trimethylolpropane triacrylate, hexanediol diacrylate, tetraethylene glycol diacrylate, pentaerythritol tetraacrylate, sorbitol triacrylate, isocyanuric acid ethylene oxide (EO) modified triacrylate, polyester acrylate oligomer, etc. Specific examples of methacrylic esters include tetramethylene glycol dimethacrylate, neopentyl glycol dimethacrylate, trimethylolpropane trimethacrylate, ethylene glycol dimethacrylate, pentaerythritol trimethacrylate, bis[p-(3-methacryloxy-2-hydroxypropoxy)phenyl]dimethylmethane, bis[p-(methacryloxyethoxy)phenyl]dimethylmethane, etc. Specific examples of amide monomers of polyamine compounds and unsaturated carboxylic acids include methylene bisacrylamide, methylene bismethacrylamide, 1,6-hexamethylene bisacrylamide, 1,6-hexamethylene bismethacrylamide, diethylenetriamine trisacrylamide, xylylene bisacrylamide, and xylylene bismethacrylamide.
[0109] Also suitable are urethane-based addition polymerizable compounds produced by an addition reaction between an isocyanate and a hydroxy group. Specific examples thereof include vinyl urethane compounds containing two or more polymerizable vinyl groups in one molecule, which are obtained by adding a vinyl monomer containing a hydroxy group represented by the following formula (M) to a polyisocyanate compound having two or more isocyanate groups in one molecule, as described in JP-B-48-41708. CH2=C(R M4 )COOCH2CH(R M5 )OH (M) In formula (M), R M4 and R M5each independently represents a hydrogen atom or a methyl group.
[0110] In addition, urethane acrylates described in JP-A-51-37193, JP-B-2-32293, JP-B-2-16765, JP-A-2003-344997, and JP-A-2006-65210, JP-B-58-49860, JP-B-56-17654, JP-B-62-39417, and JP-B-62-39418 Also suitable are urethane compounds having an ethylene oxide skeleton described in JP-A-2000-250211 and JP-A-2007-94138, and urethane compounds having a hydrophilic group described in U.S. Pat. No. 7,153,632, JP-T-8-505958, JP-A-2007-293221 and JP-A-2007-293223.
[0111] Details of the method of use such as the structure of the polymerizable compound, whether it is used alone or in combination, and the amount added can be arbitrarily set in consideration of the final use of the lithographic printing plate precursor. The content of the polymerizable compound is preferably from 1 to 50% by mass, more preferably from 3 to 30% by mass, and even more preferably from 5 to 20% by mass, based on the total solid content of the image recording layer.
[0112] (polymer compound) The polymer compound may function as a binder polymer in the image recording layer, or may be present in the image recording layer as a particulate polymer compound (polymer particles).
[0113] <Binder polymer> The binder polymer is preferably a polymer having film properties, and preferred examples thereof include (meth)acrylic resin, polyvinyl acetal resin, and polyurethane resin.
[0114] The binder polymer used in the image recording layer is preferably a binder polymer having an alkylene oxide chain. The binder polymer having an alkylene oxide chain may have a poly(alkylene oxide) moiety in the main chain or in the side chain. It may also be a graft polymer having a poly(alkylene oxide) moiety in the side chain, or a block copolymer of a block composed of a repeating unit containing a poly(alkylene oxide) moiety and a block composed of a repeating unit not containing an (alkylene oxide) moiety. When the main chain has a poly(alkylene oxide) moiety, polyurethane resin is preferred. When the main chain has a poly(alkylene oxide) moiety in the side chain, examples of the polymer of the main chain include (meth)acrylic resin, polyvinyl acetal resin, polyurethane resin, polyurea resin, polyimide resin, polyamide resin, epoxy resin, polystyrene resin, novolac type phenolic resin, polyester resin, synthetic rubber, and natural rubber, and (meth)acrylic resin is particularly preferred.
[0115] The alkylene oxide is preferably an alkylene oxide having 2 to 6 carbon atoms, and ethylene oxide or propylene oxide is particularly preferred. The number of repeating alkylene oxides in the poly(alkylene oxide) moiety is preferably 2-120, more preferably 2-70, and even more preferably 2-50. If the number of alkylene oxide repetitions is 120 or less, the deterioration of printing durability due to abrasion and the deterioration of printing durability due to deterioration of ink receptivity are suppressed, which is preferable.
[0116] The poly(alkylene oxide) moiety is preferably contained as a side chain of the binder polymer in the form of a structure represented by the following formula (AO), and more preferably contained as a side chain of the (meth)acrylic resin in the form of a structure represented by the following formula (AO).
[0117] [ka]
[0118] In formula (AO), y represents 2 to 120, R1 represents a hydrogen atom or an alkyl group, and R2 represents a hydrogen atom or a monovalent organic group. The monovalent organic group is preferably an alkyl group having 1 to 6 carbon atoms, specifically, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, an n-hexyl group, an isohexyl group, a 1,1-dimethylbutyl group, a 2,2-dimethylbutyl group, a cyclopentyl group, and a cyclohexyl group. In formula (AO), y is preferably 2 to 70, more preferably 2 to 50. R1 is preferably a hydrogen atom or a methyl group, particularly preferably a hydrogen atom. R2 is particularly preferably a hydrogen atom or a methyl group.
[0119] The binder polymer may have a crosslinking property in order to improve the film strength of the image area. In order to impart crosslinking properties to the polymer, a crosslinkable functional group such as an ethylenically unsaturated bond may be introduced into the main chain or side chain of the polymer. The crosslinkable functional group may be introduced by copolymerization or by polymer reaction. Examples of the polymer having an ethylenically unsaturated bond in the main chain of the molecule include poly-1,4-butadiene and poly-1,4-isoprene. Examples of polymers having an ethylenically unsaturated bond in a side chain of the molecule include polymers of esters or amides of acrylic acid or methacrylic acid, in which the R of the ester or amide residue (-COOR or -CONHR) has an ethylenically unsaturated bond.
[0120] Examples of the residue having an ethylenically unsaturated bond (R above) include -(CH2) n CR 1A =CR 2A R 3A , -(CH2O) n CH2CR 1A =CR 2A R 3A , -(CH2CH2O) n CH2CR 1A=CR 2A R 3A , -(CH2) n NH-CO-O-CH2CR 1A =CR 2A R 3A , -(CH2) n -O-CO-CR 1A =CR 2A R 3A and -(CH2CH2O)2-X A (In the formula, R A1 ~R A3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 20 carbon atoms, an aryl group, an alkoxy group, or an aryloxy group; R A1 and R A2 or R A3 may be bonded to each other to form a ring. n represents an integer of 1 to 10. A represents a dicyclopentadienyl residue.
[0121] Specific examples of ester residues include -CH2CH=CH2, -CH2CH2O-CH2CH=CH2, -CH2C(CH3)=CH2, -CH2CH=CH-C6H5, -CH2CH2OCOCH=CH-C6H5, -CH2CH2-NHCOO-CH2CH=CH2 and -CH2CH2O-X (wherein X represents a dicyclopentadienyl residue). Specific examples of amide residues include -CH2CH=CH2, -CH2CH2-Y (wherein Y represents a cyclohexene residue) and -CH2CH2-OCO-CH=CH2.
[0122] A crosslinkable binder polymer is cured by, for example, addition of a free radical (polymerization initiation radical or a propagating radical in the polymerization process of a polymerizable compound) to its crosslinkable functional group, which undergoes addition polymerization between polymers directly or via a polymerization chain of the polymerizable compound, forming a crosslink between polymer molecules. Alternatively, an atom in the polymer (e.g., a hydrogen atom on a carbon atom adjacent to a functional crosslinking group) is abstracted by a free radical to generate a polymer radical, which then bonds to each other to form a crosslink between polymer molecules, thereby curing.
[0123] The content of the crosslinkable group in the binder polymer (the content of the radically polymerizable unsaturated double bonds determined by iodometric titration) is preferably 0.1 to 10.0 mmol, more preferably 1.0 to 7.0 mmol, and even more preferably 2.0 to 5.5 mmol, per 1 g of the binder polymer, from the viewpoints of good sensitivity and good storage stability.
[0124] Specific examples 1 to 11 of binder polymers are shown below, but the present invention is not limited thereto. In the following exemplary compounds, the numerical value shown next to each repeating unit (the numerical value shown next to the main chain repeating unit) indicates the mole percentage of the repeating unit. The numerical value shown next to the repeating unit of the side chain indicates the number of repeats of the repeating portion. In addition, Me represents a methyl group, Et represents an ethyl group, and Ph represents a phenyl group.
[0125] [ka]
[0126] [ka]
[0127] The molecular weight of the binder polymer is, in terms of polystyrene equivalent, a mass average molecular weight (Mw) measured by a GPC method of 2,000 or more, preferably 5,000 or more, and more preferably 10,000 to 300,000.
[0128] If necessary, a hydrophilic polymer such as polyacrylic acid or polyvinyl alcohol described in JP-A-2008-195018 can be used in combination. Also, a lipophilic polymer and a hydrophilic polymer can be used in combination.
[0129] The binder polymer may be used alone or in combination of two or more kinds. The content of the binder polymer is preferably from 1 to 90% by mass, and more preferably from 5 to 80% by mass, of the total solid content of the image recording layer.
[0130] <Polymer particles> The image recording layer preferably contains polymer particles. The polymer particles contribute to improving on-press developability. The polymer particles are preferably polymer particles that can convert the image recording layer to hydrophobicity when heat is applied. The polymer particles are preferably at least one selected from hydrophobic thermoplastic polymer particles, heat-reactive polymer particles, polymer particles having a polymerizable group, microcapsules containing a hydrophobic compound, and microgels (crosslinked polymer particles).
[0131] Suitable examples of the hydrophobic thermoplastic polymer particles include the hydrophobic thermoplastic polymer particles described in Research Disclosure No. 33303 published in January 1992, JP-A Nos. 9-123387, 9-131850, 9-171249, and 9-171250, and European Patent No. 931647. Specific examples of the polymer constituting the hydrophobic thermoplastic polymer particles include homopolymers or copolymers of monomers such as ethylene, styrene, vinyl chloride, methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, vinylidene chloride, acrylonitrile, vinylcarbazole, acrylates or methacrylates having a polyalkylene structure, or mixtures thereof. Preferred are polystyrene, copolymers containing styrene and acrylonitrile, and polymethyl methacrylate. The average particle size of the hydrophobic thermoplastic polymer particles is preferably 0.01 to 2.0 μm.
[0132] The thermally reactive polymer particles include polymer particles having a thermally reactive group. The polymer particles having a thermally reactive group form a hydrophobic region by crosslinking due to a thermal reaction and by the change in the functional group at that time.
[0133] The heat-reactive group in the polymer particles having a heat-reactive group can be any functional group that undergoes any reaction as long as it forms a chemical bond, and is preferably a polymerizable group.As examples thereof, the ethylenically unsaturated group that undergoes radical polymerization reaction (such as acryloyl group, methacryloyl group, vinyl group, allyl group, etc.), cationic polymerizable group (such as vinyl group, vinyloxy group, epoxy group, oxetanyl group, etc.), the isocyanato group or its block product that undergoes addition reaction, epoxy group, vinyloxy group and the functional group with active hydrogen atom that is their reaction partner (such as amino group, hydroxyl group, carboxyl group, etc.), the carboxyl group that undergoes condensation reaction and the hydroxyl group or amino group that is their reaction partner, the acid anhydride that undergoes ring-opening addition reaction and the amino group or hydroxyl group that is their reaction partner can be suitably mentioned.
[0134] As the microcapsule, for example, as described in JP-A-2001-277740 and JP-A-2001-277742, all or part of the components of the image recording layer are encapsulated in the microcapsule. The components of the image recording layer can also be contained outside the microcapsule. As the image recording layer containing the microcapsule, a preferred embodiment is one in which the hydrophobic components are encapsulated in the microcapsule and the hydrophilic components are contained outside the microcapsule.
[0135] The microgel (crosslinked polymer particle) can contain a part of the constituent components of the image recording layer in at least one of its interior and surface. In particular, an embodiment in which the microgel has a radical polymerizable group on its surface to form a reactive microgel is preferred from the viewpoint of image formation sensitivity and printing durability.
[0136] In order to microencapsulate or microgel the components of the image recording layer, known methods can be used. The average particle size of the microcapsules or microgels is preferably 0.01 to 3.0 μm, more preferably 0.05 to 2.0 μm, and particularly preferably 0.10 to 1.0 μm. Good resolution and stability over time can be obtained within this range.
[0137] The polymer particles may be used alone or in combination of two or more kinds. The content of the polymer particles is preferably from 5 to 90% by mass, more preferably from 5 to 80% by mass, and even more preferably from 10 to 75% by mass, based on the total solid content of the image recording layer.
[0138] The polymer compound contained in the image recording layer is preferably a polymer compound containing a structural unit derived from a styrene compound and / or a structural unit derived from an acrylonitrile compound. From the viewpoint of contributing to on-press developability, this polymer compound can be suitably used as a binder polymer or polymer particles.
[0139] Examples of the styrene compound include styrene, p-methylstyrene, p-methoxystyrene, β-methylstyrene, p-methyl-β-methylstyrene, α-methylstyrene, and p-methoxy-β-methylstyrene, with styrene being preferred.
[0140] Examples of the acrylonitrile compound include acrylonitrile and methacrylonitrile, with acrylonitrile being preferred.
[0141] In a polymer compound containing a styrene compound and an acrylonitrile compound as constituent units, the composition ratio of the constituent units derived from the styrene compound and the constituent units derived from the acrylonitrile compound is preferably 4:1 to 1:4.
[0142] The image recording layer may contain a chain transfer agent, a low molecular weight hydrophilic compound, an oil sensitizer, and other components.
[0143] (Chain transfer agent) The chain transfer agent contributes to improving the printing durability of a lithographic printing plate prepared from the lithographic printing plate precursor. The chain transfer agent is preferably a thiol compound, more preferably a thiol having 7 or more carbon atoms in terms of boiling point (difficulty of volatilization), and further preferably a compound having a mercapto group on an aromatic ring (aromatic thiol compound). The thiol compound is preferably a monofunctional thiol compound.
[0144] Specific examples of the chain transfer agent include the following compounds.
[0145] [ka]
[0146] [ka]
[0147] [ka]
[0148] [ka]
[0149] The chain transfer agent may be used alone or in combination of two or more kinds. The content of the chain transfer agent is preferably from 0.01 to 50% by mass, more preferably from 0.05 to 40% by mass, and even more preferably from 0.1 to 30% by mass, based on the total solid content of the image recording layer.
[0150] (Low molecular hydrophilic compound) The low molecular weight hydrophilic compound contributes to improving the on-press developability of the lithographic printing plate precursor without reducing the printing durability of the lithographic printing plate produced from the lithographic printing plate precursor. The low molecular weight hydrophilic compound is preferably a compound having a molecular weight of less than 1,000, more preferably a compound having a molecular weight of less than 800, and even more preferably a compound having a molecular weight of less than 500. Examples of low molecular weight hydrophilic compounds include water-soluble organic compounds such as glycols and their ether or ester derivatives, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, and tripropylene glycol; polyols, such as glycerin, pentaerythritol, and tris(2-hydroxyethyl)isocyanurate; organic amines and their salts, such as triethanolamine, diethanolamine, and monoethanolamine; organic sulfonic acids and their salts, such as alkylsulfonic acid, toluenesulfonic acid, and benzenesulfonic acid; organic sulfamic acids and their salts, such as alkylsulfamic acid; organic sulfuric acids and their salts, such as alkylsulfuric acid and alkyl ether sulfuric acid; organic phosphonic acids and their salts, such as phenylphosphonic acid; organic carboxylic acids and their salts, such as tartaric acid, oxalic acid, citric acid, malic acid, lactic acid, gluconic acid, and amino acids; and betaines.
[0151] The low molecular weight hydrophilic compound is preferably at least one selected from polyols, organic sulfates, organic sulfonates, and betaines.
[0152] Specific examples of organic sulfonates include alkyl sulfonates such as sodium n-butyl sulfonate, sodium n-hexyl sulfonate, sodium 2-ethylhexyl sulfonate, sodium cyclohexyl sulfonate, and sodium n-octyl sulfonate; alkyl sulfonates containing an ethylene oxide chain such as sodium 5,8,11-trioxapentadecane-1-sulfonate, sodium 5,8,11-trioxaheptadecane-1-sulfonate, sodium 13-ethyl-5,8,11-trioxaheptadecane-1-sulfonate, and sodium 5,8,11,14-tetraoxatetracosane-1-sulfonate. Sulfonates: arylsulfonates such as sodium benzenesulfonate, sodium p-toluenesulfonate, sodium p-hydroxybenzenesulfonate, sodium p-styrenesulfonate, sodium isophthalate dimethyl-5-sulfonate, sodium 1-naphthylsulfonate, sodium 4-hydroxynaphthylsulfonate, disodium 1,5-naphthalenedisulfonate, and trisodium 1,3,6-naphthalenetrisulfonate; and compounds described in paragraphs 0026 to 0031 of JP-A No. 2007-276454 and paragraphs 0020 to 0047 of JP-A No. 2009-154525. The salt may be a potassium salt or a lithium salt.
[0153] The organic sulfates include sulfates of alkyl, alkenyl, alkynyl, aryl, or heterocyclic monoethers of polyethylene oxide. The number of ethylene oxide units is preferably 1 to 4, and the salt is preferably a sodium salt, a potassium salt, or a lithium salt. Specific examples include the compounds described in paragraphs 0034 to 0038 of JP-A-2007-276454.
[0154] As the betaines, compounds in which the number of carbon atoms in the hydrocarbon substituent on the nitrogen atom is 1 to 5 are preferable, and specific examples include trimethylammonium acetate, dimethylpropylammonium acetate, 3-hydroxy-4-trimethylammoniobutyrate, 4-(1-pyridinio)butyrate, 1-hydroxyethyl-1-imidazolioacetate, trimethylammonium methanesulfonate, dimethylpropylammonium methanesulfonate, 3-trimethylammonio-1-propanesulfonate, and 3-(1-pyridinio)-1-propanesulfonate.
[0155] Since the hydrophobic portion of a low molecular weight hydrophilic compound has a small structure and has almost no surfactant effect, the dampening water does not penetrate into the exposed areas (image areas) of the image recording layer, thereby preventing a decrease in the hydrophobicity or film strength of the image areas, and the ink receptivity and printing durability of the image recording layer can be maintained at a good level.
[0156] The low molecular weight hydrophilic compounds may be used alone or in combination of two or more kinds. The content of the low molecular weight hydrophilic compound is preferably from 0.5 to 20% by mass, more preferably from 1 to 15% by mass, and even more preferably from 2 to 10% by mass, based on the total solid content of the image recording layer.
[0157] (Oil Sensitizer) The oil sensitizer contributes to improving the ink receptivity (hereinafter also simply referred to as "ink receptivity") of a lithographic printing plate prepared from the lithographic printing plate precursor. Examples of the oil sensitizer include phosphonium compounds, nitrogen-containing low molecular weight compounds, and ammonium group-containing polymers. In particular, when the lithographic printing plate precursor has a protective layer containing an inorganic layered compound, these compounds function as a surface coating agent for the inorganic layered compound and have the function of suppressing a decrease in ink receptivity during printing caused by the inorganic layered compound. As the oil sensitizer, it is preferable to use a phosphonium compound, a nitrogen-containing low molecular weight compound, and an ammonium group-containing polymer in combination, and it is more preferable to use a phosphonium compound, a quaternary ammonium salt, and an ammonium group-containing polymer in combination.
[0158] Examples of the phosphonium compound include those described in JP-A-2006-297907 and JP-A-2007-50660.Specific examples include tetrabutylphosphonium iodide, butyltriphenylphosphonium bromide, tetraphenylphosphonium bromide, 1,4-bis(triphenylphosphonio)butane=di(hexafluorophosphate), 1,7-bis(triphenylphosphonio)heptane=sulfate, and 1,9-bis(triphenylphosphonio)nonane=naphthalene-2,7-disulfonate.
[0159] Examples of the nitrogen-containing low molecular weight compound include amine salts and quaternary ammonium salts. Examples of the nitrogen-containing low molecular weight compound include imidazolinium salts, benzimidazolinium salts, pyridinium salts, and quinolinium salts. Among them, quaternary ammonium salts and pyridinium salts are preferred. Specific examples include tetramethylammonium hexafluorophosphate, tetrabutylammonium hexafluorophosphate, dodecyltrimethylammonium p-toluenesulfonate, benzyltriethylammonium hexafluorophosphate, benzyldimethyloctylammonium hexafluorophosphate, benzyldimethyldodecylammonium hexafluorophosphate, and the compounds described in paragraphs 0021 to 0037 of JP-A-2008-284858 and paragraphs 0030 to 0057 of JP-A-2009-90645.
[0160] The ammonium group-containing polymer may have an ammonium group in its structure, and is preferably a polymer containing 5 to 80 mol % of a (meth)acrylate having an ammonium group in a side chain as a copolymerization component. Specific examples include the polymers described in paragraphs 0089 to 0105 of JP-A No. 2009-208458.
[0161] The ammonium group-containing polymer preferably has a reduced specific viscosity (unit: ml / g) value determined according to the measurement method described in JP 2009-208458 A in the range of 5 to 120, more preferably in the range of 10 to 110, and particularly preferably in the range of 15 to 100. When the reduced specific viscosity is converted into a weight average molecular weight (Mw), it is preferably 10,000 to 150,0000, more preferably 17,000 to 140,000, and particularly preferably 20,000 to 130,000.
[0162] Specific examples of the ammonium group-containing polymer are shown below. (1) 2-(trimethylammonio)ethyl methacrylate = p-toluenesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 10 / 90, Mw 45,000) (2) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (3) 2-(ethyldimethylammonio)ethyl methacrylate = p-toluenesulfonate / hexyl methacrylate copolymer (molar ratio 30 / 70, Mw 45,000) (4) 2-(trimethylammonio)ethyl methacrylate = hexafluorophosphate / 2-ethylhexyl methacrylate copolymer (molar ratio 20 / 80, Mw 60,000) (5) 2-(trimethylammonio)ethyl methacrylate = methyl sulfate / hexyl methacrylate copolymer (molar ratio 40 / 60, Mw 70,000) (6) 2-(butyldimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 25 / 75, Mw 65,000) (7) 2-(butyldimethylammonio)ethyl acrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 65,000) (8) 2-(butyldimethylammonio)ethyl methacrylate = 13-ethyl-5,8,11-trioxa-1-heptadecanesulfonate / 3,6-dioxaheptyl methacrylate copolymer (molar ratio 20 / 80, Mw 75,000) (9) 2-(butyldimethylammonio)ethyl methacrylate = hexafluorophosphate / 3,6-dioxaheptyl methacrylate / 2-hydroxy-3-methacryloyloxypropyl methacrylate copolymer (molar ratio 15 / 80 / 5, Mw 65,000)
[0163] The content of the oil sensitizer is preferably from 0.01 to 30% by mass, more preferably from 0.1 to 15% by mass, and even more preferably from 1 to 10% by mass, based on the total solid content of the image recording layer.
[0164] (Other Ingredients) The image recording layer may contain other components such as a surfactant, a print-out agent, a polymerization inhibitor, a higher fatty acid derivative, a plasticizer, inorganic particles, an inorganic layer compound, etc. Specifically, the above-mentioned components described in paragraphs 0114 to 0159 of JP-A-2008-284817 can be used.
[0165] The image recording layer may contain a specific hydroxy acid compound. In this case, the image recording layer corresponds to the specific component layer.
[0166] (Formation of Image Recording Layer) The image recording layer can be formed, for example, as described in paragraphs 0142 to 0143 of JP-A-2008-195018, by dispersing or dissolving the necessary components in a known solvent to prepare a coating solution, applying the coating solution by a known method such as bar coater coating, and drying. The coating amount (solid content) of the image recording layer after coating and drying varies depending on the application, but from the viewpoint of obtaining good sensitivity and good film properties of the image recording layer, it is 0.3 to 3.0 g / m 2 degree is preferred.
[0167] The on-press development type lithographic printing plate precursor can have an undercoat layer (sometimes called an intermediate layer) between the image recording layer and the support, and a protective layer (sometimes called an overcoat layer) on the image recording layer.
[0168] [Undercoat layer] The undercoat layer strengthens the adhesion between the support and the image recording layer in the exposed area and facilitates peeling of the image recording layer from the support in the unexposed area, thereby contributing to improving developability without impairing printing durability. In addition, in the case of infrared laser exposure, the undercoat layer functions as a heat insulating layer, thereby preventing the heat generated by exposure from diffusing to the support and decreasing the sensitivity.
[0169] The compound used in the undercoat layer may be a polymer having an adsorptive group and a hydrophilic group that can be adsorbed to the support surface. In order to improve adhesion with the image recording layer, a polymer having an adsorptive group and a hydrophilic group and further having a crosslinkable group is preferred. The compound used in the undercoat layer may be a low molecular weight compound or a polymer. The compound used in the undercoat layer may be a mixture of two or more kinds, if necessary.
[0170] When the compound used in the undercoat layer is a polymer, it is preferably a copolymer of a monomer having an adsorptive group, a monomer having a hydrophilic group, and a monomer having a crosslinkable group. The adsorptive group capable of being adsorbed to the surface of the support is preferably a phenolic hydroxy group, a carboxy group, -PO3H2, -OPO3H2, -CONHSO2-, -SO2NHSO2-, or -COCH2COCH3. The hydrophilic group is preferably a sulfo group or a salt thereof, or a salt of a carboxy group. The crosslinkable group is preferably an acryl group, a methacryl group, an acrylamide group, a methacrylamide group, or an allyl group. The polymer may have a crosslinkable group introduced by salt formation between a polar substituent of the polymer and a compound having an ethylenically unsaturated bond and a substituent having an opposite charge to the polar substituent, or may further be copolymerized with a monomer other than the above, preferably a hydrophilic monomer.
[0171] Specifically, preferred examples include a silane coupling agent having an addition-polymerizable ethylenic double bond reactive group described in JP-A-10-282679, and a phosphorus compound having an ethylenic double bond reactive group described in JP-A-2-304441. Also preferred are low-molecular or high-molecular compounds having a crosslinkable group (preferably an ethylenic unsaturated bond group), a functional group that interacts with the support surface, and a hydrophilic group described in JP-A-2005-238816, JP-A-2005-125749, JP-A-2006-239867, and JP-A-2006-215263. More preferred examples include polymers having an adsorptive group, a hydrophilic group and a crosslinkable group capable of being adsorbed onto the surface of a support, as described in JP-A Nos. 2005-125749 and 2006-188038.
[0172] The content of the ethylenically unsaturated bond group in the polymer used in the undercoat layer is preferably 0.1 to 10.0 mmol, more preferably 0.2 to 5.5 mmol, per 1 g of the polymer. The mass average molecular weight (Mw) of the polymer used in the undercoat layer is preferably 5,000 or more, and more preferably from 10,000 to 300,000.
[0173] In addition to the above-mentioned compounds for the undercoat layer, the undercoat layer may contain a chelating agent, a secondary or tertiary amine, a polymerization inhibitor, a compound having an amino group or a functional group having polymerization inhibitory ability and a group that interacts with the support surface (e.g., 1,4-diazabicyclo[2.2.2]octane (DABCO), 2,3,5,6-tetrahydroxy-p-quinone, chloranil, sulfophthalic acid, hydroxyethylethylenediaminetriacetic acid, dihydroxyethylethylenediaminediacetic acid, hydroxyethyliminodiacetic acid, etc.) to prevent contamination over time.
[0174] The undercoat layer may contain a specific hydroxy acid compound. In this case, the undercoat layer corresponds to the specific constituent layer.
[0175] The undercoat layer can be formed by coating and drying using a known method. The coating amount (solid content) of the undercoat layer after drying is 0.1 to 100 mg / m 2 is preferable, and 1 to 30 mg / m 2 is more preferred.
[0176] [Protective layer] The protective layer has a function of suppressing reactions that inhibit image formation by blocking oxygen, as well as a function of preventing the occurrence of scratches in the image recording layer and ablation during exposure to high-intensity laser light.
[0177] A protective layer having such characteristics is described, for example, in U.S. Pat. No. 3,458,311 and Japanese Patent Publication No. 55-49729. As the low oxygen permeability polymer used in the protective layer, either a water-soluble polymer or a water-insoluble polymer can be appropriately selected and used, and two or more types can be mixed and used as necessary. Specific examples include polyvinyl alcohol resins (including polyvinyl alcohol and modified polyvinyl alcohol), polyvinylpyrrolidone, water-soluble cellulose derivatives, poly(meth)acrylonitrile, etc. The polyvinyl alcohol is preferably one having a degree of saponification of 50% or more. The degree of saponification of polyvinyl alcohol is preferably 60% or more, more preferably 70% or more, and even more preferably 85% or more. There is no particular upper limit to the degree of saponification, and the degree of saponification may be 100% or less. The degree of saponification can be measured according to the method described in JIS K 6726:1994. The modified polyvinyl alcohol is preferably an acid-modified polyvinyl alcohol having a carboxy group or a sulfo group, specifically, the modified polyvinyl alcohols described in JP-A-2005-250216 and JP-A-2006-259137. Among the water-soluble polymers, polyvinyl alcohol resins are preferred.
[0178] The protective layer preferably contains an inorganic layered compound to improve the oxygen barrier properties. The inorganic layered compound is a thin, tabular particle, and examples thereof include mica such as natural mica and synthetic mica, talc represented by the formula: 3MgO·4SiO·H2O, taeniolite, montmorillonite, saponite, hectorite, and zirconium phosphate. The inorganic layered compound preferably used is a mica compound. Examples of the mica compound include those represented by the formula: A(B,C) 2-5 D4O 10 Examples of mica include natural mica and synthetic mica represented by the formula (OH,F,O)2 (wherein A is K, Na, or Ca, B and C are Fe(II), Fe(III), Mn, Al, Mg, or V, and D is Si or Al).
[0179] In the mica group, natural micas include muscovite, sodalite, phlogopite, biotite and lepidolite. Synthetic micas include fluorphlogopite KMg3(AlSi3O 10 )F2, potassium tetrasilicic mica KMg 2.5 SiO 10 )F2 and other non-swelling micas, and Na tetrasilicic mica NaMg 2.5 (SiO 10 )F2, Na or Li taeniolite (Na,Li)Mg2Li(SiO 10 ) F2, Na or Li hectorite of the montmorillonite series (Na, Li) 1 / 8 Mg 2 / 5 Li 1 / 8 (SiO 10 ) F2 and other swelling micas. Synthetic smectite is also useful.
[0180] Among mica compounds, fluorine-based swellable mica is particularly useful. That is, swellable synthetic mica has a layered structure consisting of unit crystal lattice layers with a thickness of about 10 to 15 Å, and the metal atom substitution within the lattice is significantly larger than that of other clay minerals. As a result, the lattice layers have a positive charge deficiency, and to compensate for this, Li + , Na + , Ca 2+ , Mg 2+The cations present between the layers are called exchangeable cations and can be exchanged with various other cations. In particular, the cations present between the layers are Li + , Na + In the case of , the bond between the layered crystal lattices is weak due to the small ionic radius, and it swells greatly in water. When shear is applied in this state, it easily cleaves and forms a stable sol in water. Swellable synthetic mica has a strong tendency in this case, and is particularly preferred.
[0181] As for the shape of the mica compound, from the viewpoint of diffusion control, the thinner the thickness, the better, and the larger the planar size, the better, as long as it does not impede the smoothness of the coating surface or the transmittance of actinic rays. Therefore, the aspect ratio is preferably 20 or more, more preferably 100 or more, and particularly preferably 200 or more. The aspect ratio is the ratio of the major axis to the thickness of the particle, and can be measured, for example, from a projection of the particle in a microscopic photograph. The larger the aspect ratio, the greater the effect obtained.
[0182] The particle size of the mica compound is preferably 0.3 to 20 μm, more preferably 0.5 to 10 μm, and particularly preferably 1 to 5 μm in terms of average major axis. The average thickness of the particles is preferably 0.1 μm or less, more preferably 0.05 μm or less, and particularly preferably 0.01 μm or less. Specifically, for example, in the case of swellable synthetic mica, which is a representative compound, the preferred embodiment is that the thickness is about 1 to 50 nm, and the face size (major axis) is about 1 to 20 μm.
[0183] The content of the inorganic layered compound is preferably 0 to 60% by mass, more preferably 3 to 50% by mass, based on the total solid content of the protective layer. Even when a plurality of inorganic layered compounds are used in combination, the total amount of the inorganic layered compounds is preferably within the above content. Within the above range, oxygen barrier properties are improved and good sensitivity is obtained. Also, deterioration of ink receptivity can be prevented.
[0184] The protective layer may contain known additives such as a plasticizer for imparting flexibility, a surfactant for improving coatability, inorganic fine particles for controlling surface slippage, etc. Furthermore, the protective layer may contain an oil sensitizer described in the image recording layer.
[0185] The protective layer may contain a specific hydroxy acid compound. In this case, the protective layer corresponds to the specific constituent layer.
[0186] The protective layer can be formed by coating and drying using a known method. The coating amount (solid content) of the protective layer after drying is 0.01 to 10 g / m 2 is preferable, and 0.02 to 3 g / m 2 More preferably, 0.02 to 1 g / m 2 is particularly preferred.
[0187] [Discarded original version] A disposable printing plate precursor, which is another embodiment of the on-press development type printing plate precursor according to the present invention, will be described below. A throwaway plate precursor is a plate for producing a throwaway plate through the same platemaking process as a lithographic printing plate precursor (however, image exposure is not required), and does not basically have photosensitivity. As is well known in the printing industry, throwaway plates are attached to a plate cylinder when, for example, in color newspaper printing (multicolor printing), it is necessary to print part of the page in two colors or one color.
[0188] The sacrificial plate precursor has a non-photosensitive layer on the aluminum support having the above-mentioned anodized film. Here, "non-photosensitive" means that it has substantially no photosensitivity to light from a light source used in the image exposure process of a normal lithographic printing plate precursor that is used in a printing process together with the sacrificial plate precursor. "Substantially no photosensitivity" means that no polymerization reaction occurs within the range in which the sacrificial plate precursor is normally used. In the throwaway master, all of the constituent layers are non-photosensitive.
[0189] (Non-photosensitive layer) The non-photosensitive layer is a layer that can be removed on a printing press by at least one of an acidic to alkaline dampening water and a printing ink. The non-photosensitive layer may contain a resin. The resin is mainly used for the purpose of improving the film strength of the non-photosensitive layer. The resin contained in the non-photosensitive layer may be a conventionally known resin used as a binder polymer in the image recording layer of a normal lithographic printing plate precursor, and is preferably a resin having film properties. Among them, acrylic resin, polyvinyl acetal resin, polyurethane resin, etc. are preferred.
[0190] The resin contained in the non-photosensitive layer preferably has a hydrophilic group, which contributes to imparting on-press developability to the non-photosensitive layer. Examples of the hydrophilic group include a hydroxy group, a carboxy group, an alkylene oxide structure, an amino group, an ammonium group, an amide group, a sulfo group, and a phosphate group, and among these, an alkylene oxide structure having 1 to 9 alkylene oxide units each having 2 or 3 carbon atoms is preferred. To impart a hydrophilic group to a resin, for example, a monomer having a hydrophilic group can be copolymerized.
[0191] A preferred example of the resin contained in the non-photosensitive layer is a polymer compound having a polyoxyalkylene chain in the side chain. By containing a polymer compound having a polyoxyalkylene chain in the side chain in the non-photosensitive layer, the permeability of the dampening water is promoted, and the on-press developability is improved. Other preferred examples of the polymer compound having a polyoxyalkylene chain in the side chain and the resin contained in the non-photosensitive layer are described in paragraphs 0085 to 0102 of JP2017-65184A.
[0192] The resin contained in the non-photosensitive layer preferably has a mass average molecular weight (Mw) of 2,000 or more, more preferably 5,000 or more, and further preferably from 10,000 to 300,000.
[0193] The content of the resin contained in the non-photosensitive layer is suitably 3 to 90% by mass, preferably 5 to 80% by mass, and more preferably 10 to 70% by mass, based on the total solid content of the non-photosensitive layer.
[0194] The non-photosensitive layer may further contain, as necessary, a surfactant, a colorant, a print-out agent, a polymerization inhibitor, a higher fatty acid derivative, a plasticizer, inorganic fine particles, an inorganic layer compound, a co-sensitizer, a chain transfer agent, etc. Specifically, the compounds and the amounts of addition described in paragraphs
[0114] to
[0159] of JP-A No. 2008-284817, paragraphs
[0023] to
[0027] of JP-A No. 2006-091479, and paragraph
[0060] of U.S. Patent Publication No. 2008 / 0311520 can be preferably used.
[0195] The non-photosensitive layer may contain a specific hydroxy acid compound. In this case, the non-photosensitive layer corresponds to the specific component layer.
[0196] (Formation of non-photosensitive layer) The non-photosensitive layer can be formed by preparing a coating solution by dispersing or dissolving the necessary components in a known solvent, applying the coating solution by a known method such as bar coater coating, and drying. The coating amount (solid content) of the non-photosensitive layer after drying is 0.05 to 1.0 g / m from the viewpoint of both on-machine developability and scratch resistance. 2 is preferably 0.1 to 0.7 g / m 2 is more preferred.
[0197] In the throwaway plate precursor, the non-photosensitive layer may be provided directly on the aluminum support having an anodized film, or may be provided on an undercoat layer provided on the aluminum support having an anodized film. As the undercoat layer, the undercoat layer described for the on-press development type lithographic printing plate precursor can be used. The sacrificial plate precursor may further have a protective layer on the non-photosensitive layer. As the protective layer, the protective layers described in relation to the on-press development type lithographic printing plate precursor can be used.
[0198] The on-press development type printing plate precursor according to the present invention has a droop shape at the edge portion.
[0199] FIG. 3 is a schematic diagram showing the cross-sectional shape of an edge portion of a lithographic printing plate precursor, which is one embodiment of a printing plate precursor. 3, the lithographic printing plate precursor 1 has a sag 2 at its edge. The distance X from the upper end of an edge surface 1c of the lithographic printing plate precursor 1 (the boundary point between the sag 2 and the edge surface 1c) to the intersection point between an extension of the edge surface 1c and an extension of the image recording layer surface (protective layer surface if a protective layer is formed) 1a is referred to as the "sag amount X," and the distance Y from the point where the image recording layer surface 1a of the lithographic printing plate precursor 1 starts to sag to the intersection point is referred to as the "sag width Y."
[0200] In the sagging shape of the edge, the sagging amount X is preferably 25 μm or more, more preferably 35 μm or more, and even more preferably 40 μm or more. The upper limit of the sagging amount X is preferably 150 μm from the viewpoint of preventing deterioration of on-machine developability due to deterioration of the edge surface condition. When on-machine developability deteriorates, ink may adhere to the remaining image recording layer, which may cause edge staining. If the sagging amount X is too small, the ink adhered to the edge may be easily transferred to the blanket, which may cause edge staining. When the sagging amount X is in the range of 25 to 150 μm, if the sagging width Y is small, the occurrence of cracks at the edge increases, and printing ink may accumulate there, which may cause edge staining. From this viewpoint, the sagging width Y is preferably in the range of 70 to 300 μm, and more preferably in the range of 80 to 250 μm. The above sagging amount and sagging width ranges are not related to the edge shape of the support surface 1b of the lithographic printing plate precursor 1. Usually, at the edge of the lithographic printing plate precursor 1, sagging occurs at the boundary B between the image recording layer and the support, and on the support surface 1b, similar to the image recording layer surface 1a.
[0201] The formation of the end portion having the above-mentioned drooped shape can be achieved, for example, by adjusting the cutting conditions of the printing plate precursor. Specifically, this can be achieved by adjusting the gap between the upper and lower cutting blades, the amount of engagement, the blade angle, etc., of the slitter device used when cutting the printing plate master. FIG. 4 is a conceptual diagram showing an example of the cutting section of a slitter device. In the slitter device, a pair of upper and lower cutting blades 10 and 20 are arranged vertically. The cutting blades 10 and 20 are circular blades on a disk, and the upper cutting blades 10a and 10b are supported coaxially on a rotating shaft 11, and the lower cutting blades 20a and 20b are supported coaxially on a rotating shaft 21. The upper cutting blades 10a and 10b and the lower cutting blades 20a and 20b are rotated in opposite directions. The printing plate 30 is cut to a predetermined width by passing between the upper cutting blades 10a and 10b and the lower cutting blades 20a and 20b. An end portion having a drooped shape can be formed by adjusting the gap between the upper cutting blade 10a and the lower cutting blade 20a and the gap between the upper cutting blade 10b and the lower cutting blade 20b in the cutting section of the slitter device.
[0202] In the on-press development type printing plate precursor according to the present invention, the arithmetic mean height Sa of the outermost layer surface on the side opposite to the side having the specific component layer is preferably 0.3 to 20 μm. Here, the side opposite to the side having the specific component layer means the side opposite to the side having the specific component layer with respect to the aluminum support. In the on-press development type printing plate precursor according to the present invention, the arithmetic mean height Sa of the outermost layer surface on the side having the specific component layer is preferably 0.3 to 20 μm. Here, the side having the specific component layer means the side having the specific component layer with respect to the aluminum support. By providing an outermost layer surface having such characteristics, the on-press development type printing master plate of the present invention, even when stacked in a form where no interleaf paper is sandwiched between the master plates (also called interleaf-less), is excellent in performance, such as preventing multiple feeding in the process of removing the master plates from the stack, preventing scratches caused by the convex portions provided on the outermost layer surface of the master plate, and preventing development delays caused by the convex portions provided on the outermost layer surface of the master plate.
[0203] The outermost surface on the side opposite to the side having the specific component layer is the surface of the backcoat layer if a backcoat layer is present on the opposite side, and is the surface of the support if no layer is present on the opposite side. For example, when forming the protrusions described below, the printing plate may have the backcoat layer as the outermost layer and have a plurality of protrusions containing a polymer compound on the backcoat layer, or the support may have the support as the outermost layer and have a plurality of protrusions containing a polymer compound on the support.
[0204] When the image recording layer or the protective layer is the outermost layer, the outermost surface on the side having the specific component layer is the surface of the image recording layer or the surface of the protective layer. For example, when forming protrusions as described below, the printing plate precursor may have the image recording layer or protective layer as the outermost layer, and may have a plurality of protrusions containing a polymer compound on the image recording layer or protective layer.
[0205] The arithmetic mean height Sa of the outermost layer surface on the side opposite to the side having the specific component layer is more preferably 0.5 to 10 μm, and further preferably 0.5 to 7 μm. The arithmetic mean height Sa of the outermost layer surface on the side having the specific component layer is more preferably 0.5 to 10 μm, and further preferably 0.5 to 7 μm.
[0206] The arithmetic mean height Sa of the outermost layer surface is measured according to the method described in ISO 25178. Specifically, three or more locations are selected from the same sample and measured using a Micromap MM3200-M100 manufactured by Ryoka Systems Co., Ltd., and the average of these measurements is taken as the arithmetic mean height Sa. The measurement range is a 1 cm x 1 cm area randomly selected from the sample surface.
[0207] In order to achieve the requirement that the arithmetic mean height Sa of the outermost layer surface be 0.3 to 20 μm, it is preferable that the outermost layer be formed into a shape having projections and recesses. Specifically, for example, the outermost layer may contain particles having an average particle size of 0.5 to 20 μm (Mode 1), and the outermost layer may have a plurality of protrusions containing a polymer compound as a main component (Mode 2). Here, the main component refers to the component with the highest content ratio (mass %).
[0208] In embodiment 1, the particles having an average particle size of 0.5 to 20 μm are not particularly limited, but are preferably at least one type of particles selected from organic resin particles and inorganic particles.
[0209] Preferred examples of the organic resin particles include particles made of synthetic resins such as poly(meth)acrylic acid esters, polystyrene and derivatives thereof, polyamides, polyimides, polyolefins such as low-density polyethylene, high-density polyethylene, and polypropylene, polyurethanes, polyureas, and polyesters, and particles made of natural polymers such as chitin, chitosan, cellulose, crosslinked starch, and crosslinked cellulose. Among these, synthetic resin particles have the advantages that the particle size can be easily controlled and that the desired surface properties can be easily controlled by surface modification.
[0210] Regarding the method of producing organic resin particles, for relatively hard resins such as polymethyl methacrylate (PMMA), it is possible to make fine particles by a crushing method, but the method of synthesizing particles by emulsion suspension polymerization is preferably adopted because of the ease and precision of particle size control. Methods for producing organic resin particles are described in detail in, for example, "Ultrafine particles and materials" edited by the Society of Materials Science of Japan, published by Shokabo in 1993, and "Preparation and Applications of Fine Particles and Powders" edited by Haruma Kawaguchi, published by CMC Publishing in 2005.
[0211] The organic resin particles are also available as commercially available products. For example, cross-linked acrylic resins MX-40T, MX-80H3wT, MX-150, MX-180TA, MX-300, MX-500, MX-1000, MX-1500H, MR-2HG, MR-7HG, MR-10HG, MR-3GSN, MR-5GSN, MR-7G, MR-10G, MR-5C, and MR-7GC manufactured by Soken Chemical & Engineering Co., Ltd.; styryl resin-based SX-350H and SX-500H manufactured by Sekisui Chemical Co., Ltd. Examples of such polyolefin resins include polyolefin resins manufactured by Mitsui Chemicals, Inc., and Chemipearl W100, W200, W300, W308, W310, W400, W401, W405, W410, W500, WF640, W700, W800, W900, W950, and WP100.
[0212] Examples of inorganic particles include silica, alumina, zirconia, titania, carbon black, graphite, BaSO4, ZnS, MgCO3, CaCO3, ZnO, CaO, WS2, MoS2, MgO, SnO2, α-Fe2O3, α-FeOOH, SiC, CeO2, BN, SiN, MoC, BC, WC, titanium carbide, corundum, artificial diamond, garnet, silica, tribolith, diatomaceous earth, and dolomite.
[0213] The particles are preferably particles having a hydrophilic surface, and include organic resin particles having a hydrophilic surface and inorganic particles having a hydrophilic surface. The organic resin particles having a hydrophilic surface are preferably organic resin particles coated with at least one inorganic compound selected from the group consisting of silica, alumina, titania and zirconia, and more preferably organic resin particles coated with silica. The organic resin constituting the organic resin particles having a hydrophilic surface is preferably at least one resin selected from the group consisting of polyacrylic resins, polyurethane resins, polystyrene resins, polyester resins, epoxy resins, phenolic resins and melamine resins.
[0214] Below, organic resin particles having a hydrophilic surface will be described in detail using organic resin particles coated with silica (hereinafter also referred to as "silica-coated organic resin particles") as an example, but the organic resin particles having a hydrophilic surface are not limited thereto.
[0215] The silica-coated organic resin particles are particles made of an organic resin and are surface-coated with silica. It is preferable that the organic resin particles constituting the core do not soften or become sticky due to moisture in the air or temperature. Examples of the organic resin constituting the organic resin particles in the silica-coated organic resin particles include polyacrylic resins, polyurethane resins, polystyrene resins, polyester resins, epoxy resins, phenol resins, and melamine resins.
[0216] Preferred examples of materials for forming a silica layer that covers the surface of the silica-coated organic resin particles include compounds having an alkoxysilyl group, such as condensates of alkoxysiloxane-based compounds, in particular, siloxane-based materials, specifically, silica particles such as silica sol, colloidal silica, and silica nanoparticles. The silica-coated organic resin particles may be configured such that silica particles are attached as a solid component to the surface of the organic resin particles, or such that a siloxane-based compound layer is formed on the surface of the organic resin particles by a condensation reaction of an alkoxysiloxane-based compound.
[0217] Silica does not necessarily have to cover the entire surface of the organic resin particles, and it is preferable that the surface is covered with silica in an amount of at least 0.5% by mass or more based on the total mass of the organic resin particles. That is, the presence of silica on at least a part of the surface of the organic resin particles improves the affinity of the organic particle surface with the coexisting water-soluble polymer, for example, polyvinyl alcohol (PVA), and even when subjected to external stress, the particles are prevented from falling off, and excellent scratch resistance and ease of peeling during lamination without interleaving paper can be maintained. Therefore, the term "silica coating" also includes the state in which silica is present on at least a part of the surface of the organic resin particles. The state of silica surface coating can be confirmed by morphological observation using a scanning electron microscope (SEM) etc. Also, the amount of silica coating can be confirmed by detecting Si atoms using elemental analysis such as fluorescent X-ray analysis and calculating the amount of silica present there.
[0218] The method for producing the silica-coated organic resin particles is not particularly limited, and may be a method in which silica particles or a silica precursor compound is made to coexist with a monomer component that is the raw material of the organic resin particles and a silica surface coating layer is formed at the same time as the formation of the organic resin particles, or a method in which, after the organic resin particles are formed, silica particles are physically attached to the surface and then fixed.
[0219] An example of a method for producing silica-coated organic resin particles is given below. First, silica and raw resin (more specifically, raw resin such as a monomer capable of suspension polymerization, a prepolymer capable of suspension crosslinking, or a resin liquid, which constitutes the organic resin) are added to water containing a suspension stabilizer appropriately selected from water-soluble polymers such as polyvinyl alcohol, methyl cellulose, and polyacrylic acid, and inorganic suspension agents such as calcium phosphate and calcium carbonate, and the like, and stirred and mixed to prepare a suspension in which the silica and raw resin are dispersed. At this time, a suspension having a desired particle size can be formed by adjusting the type of suspension stabilizer, its concentration, the stirring rotation speed, etc. Next, this suspension is heated to start a reaction, and the resin raw material is suspension polymerized or suspension crosslinked to generate resin particles. At this time, the coexisting silica is fixed to the resin particles that are hardened by polymerization or crosslinking reaction, particularly near the surface of the resin particles due to its physical properties. Thereafter, the suspension is separated into solid and liquid, the suspension stabilizer attached to the particles is removed by washing, and the particles are dried. Thus, approximately spherical silica-coated organic resin particles of a desired particle size to which silica is fixed are obtained.
[0220] In this way, the conditions during suspension polymerization or suspension crosslinking can be controlled to obtain silica-coated organic resin particles of the desired particle size, or, without strictly controlling the conditions, silica-coated organic resin particles can be produced and then subjected to a mesh filtration method or the like to obtain silica-coated organic particles of the desired size.
[0221] Regarding the amounts of raw materials added in the mixture when producing silica-coated organic particles by the above method, for example, when the total amount of the raw material resin and silica is 100 parts by mass, first, 0.1 to 20 parts by mass of a suspension stabilizer is added to 200 to 800 parts by mass of water as a dispersion medium, and thoroughly dissolved or dispersed, and then the mixture of the 100 parts by mass of the raw material resin and silica is added to the liquid, and stirred while adjusting the stirring speed so that the dispersed particles have a predetermined particle size, and after this particle size adjustment, the liquid temperature is raised to 30 to 90°C, and the reaction is carried out for 1 to 8 hours.
[0222] Regarding the method for producing silica-coated organic resin particles, the above-mentioned method is only one example, and for example, silica-coated organic resin particles obtained by methods described in detail in JP-A-2002-327036, JP-A-2002-173410, JP-A-2004-307837, and JP-A-2006-38246 can also be suitably used in the present invention.
[0223] In addition, silica-coated organic resin particles are also available as commercial products.Specifically, examples of silica / melamine composite particles include Optobeads 2000M, Optobeads 3500M, Optobeads 6500M, Optobeads 10500M, Optobeads 3500S, and Optobeads 6500S manufactured by Nissan Chemical Industries, Ltd.Examples of silica / acrylic composite particles include Art Pearl G-200 transparent, Art Pearl G-400 transparent, Art Pearl G-800 transparent, Art Pearl GR-400 transparent, Art Pearl GR-600 transparent, Art Pearl GR-800 transparent, and Art Pearl J-7P manufactured by Negami Chemical Industries, Ltd. Examples of silica / urethane composite particles include Art Pearl C-400 transparent, C-800 transparent, P-800T, U-600T, U-800T, CF-600T, and CF800T, all manufactured by Negami Chemical Industries, Ltd., and Dynamic Beads CN5070D and Danplacoat THU, all manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.
[0224] The organic resin particles have been described above using silica-coated organic resin particles as an example, but the same can be said for organic resin particles coated with alumina, titania or zirconia by using alumina, titania or zirconia instead of silica.
[0225] The shape of the above particles is preferably a perfect sphere, but may also be a plate shape or a so-called spindle shape whose projected view is an ellipse.
[0226] In the first embodiment, the average particle size of the particles is preferably 0.5 to 10 μm, and more preferably 0.5 to 5 μm.
[0227] The average particle size of the particles means the volume average particle size, and the volume average particle size is measured by a laser diffraction / scattering particle size distribution analyzer. Specifically, for example, the particle size distribution analyzer "Microtrac MT-3300II" (manufactured by Nikkiso Co., Ltd.) is used for the measurement. For other particles, the average particle size is measured by the above measurement method unless otherwise specified.
[0228] In the first embodiment, the in-plane density of the particles having an average particle size of 0.5 to 20 μm is 10,000 particles / mm 2 The in-plane density is preferably 100 to 5000 pieces / mm or less. 2 , and more preferably 100 to 3000 pieces / mm 2 It is.
[0229] The in-plane density can be confirmed by observing the surface of the printing plate using a scanning electron microscope (SEM). Specifically, the surface of the printing plate is observed at five points using a scanning electron microscope (SEM), the number of particles is counted, and the observation field area is mm 2 The particle size can be calculated by converting the particle size into the number of particles per unit area and calculating the average value.
[0230] The outermost layer on the side opposite to the side having the specific component layer preferably contains a binder in addition to particles having an average particle size of 0.5 to 20 μm. Examples of the binder include novolak resins such as phenol formaldehyde resin, m-cresol formaldehyde resin, p-cresol formaldehyde resin, m- / p-mixed cresol formaldehyde resin, and phenol / cresol (m-, p-, or m- / p-mixed) mixed formaldehyde resin, resol resin, pyrogallol, acetone resin, epoxy resin, saturated copolymer polyester resin, phenoxy resin, polyvinyl acetal resin, vinylidene chloride copolymer resin, polybutene, polybutadiene, polyamide, and unsaturated copolymer polyester resin. It is preferable that the toner contains at least one selected from the group consisting of steric resin, polyurethane, polyurea, polyimide, polysiloxane, polycarbonate, epoxy resin, chlorinated polyethylene, aldehyde condensation resin of alkylphenol, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylate, carboxyvinyl polymer, acrylic resin copolymer resin, hydroxycellulose, hydroxymethylcellulose, polyvinyl alcohol, polyvinylpyrrolidone, cellulose acetate, methylcellulose, and carboxymethylcellulose. A water-insoluble resin is preferable to prevent the risk of dissolution in dampening water during on-press development.
[0231] The binder preferably contains at least one selected from the group consisting of polyurethane, acrylic resin, polystyrene, and polyethylene. In the above embodiment 1, it is preferable that the particles and the binder each independently include at least one selected from the group consisting of polyurethane, acrylic resin, polystyrene, and polyethylene.
[0232] The outermost layer on the side opposite to the side having the specific component layer may contain other components in addition to the above-mentioned particles and binder. Examples of other components include known additives, such as surfactants.
[0233] The thickness of the outermost layer on the side opposite to the side having the specific component layer is preferably 0.5 to 10 μm, more preferably 0.5 to 5 μm, and further preferably 0.5 to 3 μm.
[0234] Examples of the polymer compound constituting the multiple protrusions containing the polymer compound as a main component in the embodiment 2 include novolak resins and resol resins such as phenol formaldehyde resin, m-cresol formaldehyde resin, p-cresol formaldehyde resin, m- / p-mixed cresol formaldehyde resin, and phenol / cresol (m-, p-, or m- / p-mixed) mixed formaldehyde resin, pyrogallol acetone resin, epoxy resin, saturated copolymer polyester resin, phenoxy resin, polyvinyl acetal resin, vinylidene chloride copolymer resin, polybutene, and polybutadiene. At least one polymer compound selected from the group consisting of polyamide, unsaturated copolymer polyester resin, polyurethane, polyurea, polyimide, polysiloxane, polycarbonate, epoxy resin, chlorinated polyethylene, aldehyde condensation resin of alkylphenol, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylate, carboxyvinyl polymer, acrylic resin copolymer resin, hydroxycellulose, hydroxymethylcellulose, polyvinyl alcohol, polyvinylpyrrolidone, cellulose acetate, methylcellulose, and carboxymethylcellulose is preferred.
[0235] Among them, water-soluble polymers are more preferable from the viewpoint of excellent developability even if the detached protrusions move to the image recording layer.Specific examples thereof include polyacrylates, carboxyvinyl polymers, acrylic resin copolymer resins, hydroxycellulose, hydroxymethylcellulose, polyvinyl alcohol, modified polyvinyl alcohol, polyvinylpyrrolidone, cellulose acetate, methylcellulose, and carboxymethylcellulose. The modified polyvinyl alcohol is preferably an acid-modified polyvinyl alcohol having a carboxy group or a sulfo group, specifically, the modified polyvinyl alcohols described in JP-A-2005-250216 and JP-A-2006-259137 are preferred.
[0236] The shape and height of the protrusions are not particularly limited, but it is preferable that the arithmetic mean height Sa is 0.3 to 20 μm. The method for forming the striped protrusions (striped coating film) is not particularly limited, but the striped protrusions can be easily formed by applying a composition containing at least one selected from the group consisting of particles and polymer compounds by at least one method selected from the group consisting of a bar coating method, an inkjet printing method, a gravure printing method, a screen printing method, a spray coating method, and a slot die coating method. The method for forming the dot-shaped protrusions (dot coating film) is not particularly limited, but they can be easily formed by applying a composition containing at least one selected from the group consisting of particles and polymer compounds by at least one method selected from the group consisting of a spray coating method, an inkjet printing method, and a screen printing method. The method for forming the dashed line-shaped protrusions (dashed line coating film) is not particularly limited, but they can be easily formed by applying a composition containing at least one selected from the group consisting of particles and polymer compounds using at least one method selected from the group consisting of an inkjet printing method and a screen printing method.
[0237] Examples of the binder contained in the outermost layer in embodiment 2 include the same polymer compounds as those contained in the protrusions, and the same is true for preferred embodiments. In the second embodiment, from the viewpoint of preventing the detachment of the protrusions, it is preferable that the binder contained in the outermost layer and the polymer compound contained in the protrusions contain the same type of resin. Here, the resin being the same type means that the resin type, such as polyurethane, acrylic resin, polystyrene, or polyethylene, is the same, and it is not necessary that all the structural units in the resin are the same.
[0238] [How to make a printing plate] The method for producing a printing plate according to the present invention will be described using a lithographic printing plate precursor, which is a printing plate precursor according to the present invention. The method for producing a printing plate includes a step of exposing the lithographic printing plate precursor to light (exposure step), and a step of removing the unexposed part of the image recording layer of the lithographic printing plate precursor after the image exposure on a printing press with at least one of printing ink and dampening water (on-press development step).
[0239] [Exposure process] Image exposure is preferably carried out by a method in which digital data is scanned and exposed with an infrared laser or the like. The wavelength of the exposure light source is preferably 750 to 1,400 nm. As a light source having a wavelength of 750 to 1,400 nm, a solid-state laser or a semiconductor laser that emits infrared rays is suitable. The exposure mechanism may be any of an internal drum type, an external drum type, a flatbed type, etc. The exposure step can be carried out by a known method using a plate setter, etc. Alternatively, after the lithographic printing plate precursor is mounted on a printing press equipped with an exposure device, image exposure may be carried out on the printing press.
[0240] [On-press development process] In the on-press development step, when printing is started by supplying printing ink and fountain solution on the printing press without carrying out any development treatment on the lithographic printing plate precursor after image exposure, the unexposed parts of the lithographic printing plate precursor are removed at an early stage during printing, and the surface of the hydrophilic support is exposed, forming non-image parts. As the printing ink and fountain solution, known printing inks and fountain solutions for lithographic printing are used. Either the printing ink or the fountain solution may be supplied first to the surface of the printing plate precursor, but it is preferable to supply the printing ink first in order to prevent the fountain solution from being contaminated by the removed image recording layer components. In this manner, the lithographic printing plate precursor is developed on-machine on an offset printing press and is used as is for printing a large number of sheets.
[0241] The method for producing a printing plate according to the present invention may include other known steps in addition to the steps described above, such as a plate inspection step for checking the position and orientation of the printing plate before each step, and a confirmation step for checking the printed image after the on-press development step.
[0242] [Printing method] The printing method according to the present invention will be described using a throwaway plate as a printing plate precursor according to the present invention. The printing method includes a step of removing the non-photosensitive layer from the throwaway plate precursor on a printing press with at least one of printing ink and dampening water to prepare a throwaway plate, and a step of carrying out printing using the prepared throwaway plate. The step of preparing the throwaway plate can be carried out in the same manner as the on-press development step described above. EXAMPLES
[0243] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, "%" and "parts" mean "% by mass" and "parts by mass", respectively, unless otherwise specified. In polymer compounds, unless otherwise specified, the molecular weight is the mass average molecular weight (Mw), and the ratio of the constituent repeating units is the molar percentage. The mass average molecular weight (Mw) is a value measured as a polystyrene equivalent value by gel permeation chromatography (GPC).
[0244] [Examples 1 to 49 and Comparative Examples 1 to 6]
[0245] <Preparation of Support 1> An aluminum plate (aluminum alloy plate) of material 1S having a thickness of 0.3 mm was subjected to the following treatments (Ja) to (Jm) to manufacture a support 1. Note that a water rinsing treatment was performed between all treatment steps, and after the water rinsing treatment, the liquid was removed with a nip roller.
[0246] (Ja) Mechanical roughening treatment (brush grain method) Using the apparatus shown in Figure 5, a suspension of pumice (specific gravity 1.1 g / cm 3) was supplied to the surface of the aluminum plate as an abrasive slurry, while mechanical surface roughening was performed by using a rotating bundled brush. In Fig. 5, 31 is an aluminum plate, 32 and 34 are roller-shaped brushes (bundled brushes in this embodiment), 33 is an abrasive slurry, and 35, 36, 37 and 38 are supporting rollers. For the mechanical roughening treatment, the median diameter (μm) of the abrasive was 30μm, the number of brushes was 4, and the brush rotation speed (rpm) was 250rpm. The material of the brush bundle was 6·10 nylon, with a brush bristles diameter of 0.3mm and bristles length of 50mm. The brush was densely planted in a stainless steel cylinder with a diameter of 300mm. The distance between the two support rollers (φ200mm) below the brush bundle was 300mm. The brush bundle was pressed down until the load of the drive motor rotating the brush was 10kW more than the load before pressing the brush bundle against the aluminum plate. The brush rotation direction was the same as the movement direction of the aluminum plate.
[0247] (Jb) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda with a caustic soda concentration of 26% by mass and an aluminum ion concentration of 6.5% by mass at a temperature of 70°C. The amount of aluminum dissolved on the surface to be electrochemically roughened later was 10 g / m 2 It was.
[0248] (Jc) Desmutting treatment using an acidic aqueous solution The acidic aqueous solution was a waste solution of nitric acid used in the subsequent electrochemical graining treatment at a liquid temperature of 35° C., which was sprayed onto the aluminum plate for 3 seconds to perform a desmutting treatment.
[0249] (Jd) Electrochemical roughening treatment using nitric acid aqueous solution A continuous electrochemical roughening treatment was carried out using an AC voltage of 60 Hz. The electrolyte used was an aqueous solution of nitric acid 10.4 g / L to which aluminum nitrate was added to adjust the aluminum ion concentration to 4.5 g / L, with a liquid temperature of 35°C. The AC power waveform was as shown in Figure 1, and the time tp for the current value to reach its peak from zero was 0.8 msec, with a duty ratio of 1:1 and a trapezoidal rectangular wave AC, and electrochemical roughening treatment was carried out with a carbon electrode as the counter electrode. Ferrite was used as the auxiliary anode. The electrolytic cell shown in Figure 2 was used. The current density was 30 A / dm at the peak current value. 2 The auxiliary anode was supplied with 5% of the current from the power source. 2 ) is the total amount of electricity when the aluminum plate is the anode, and is 185C / dm 2 It was.
[0250] (Je) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda with a caustic soda concentration of 27% by mass and an aluminum ion concentration of 2.5% by mass at a temperature of 50°C. The amount of dissolved aluminum was 3.5 g / m 2 It was.
[0251] (Jf) Desmutting using an acidic aqueous solution The acidic aqueous solution, an aqueous solution having a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L at a liquid temperature of 30° C., was sprayed onto the aluminum plate for 3 seconds to carry out a desmutting treatment.
[0252] (Jg) Electrochemical roughening treatment using hydrochloric acid solution A continuous electrochemical roughening treatment was carried out using an AC voltage of 60 Hz. The electrolyte used was an aqueous solution of 6.2 g / L hydrochloric acid with aluminum chloride added to adjust the aluminum ion concentration to 4.5 g / L, with a liquid temperature of 35°C. The AC power waveform was as shown in Figure 1, and the time tp for the current value to reach its peak from zero was 0.8 msec, with a duty ratio of 1:1 and a trapezoidal rectangular wave AC, and electrochemical roughening treatment was carried out with a carbon electrode as the counter electrode. Ferrite was used as the auxiliary anode. The electrolytic cell used was as shown in Figure 2. The current density was 25 A / dm at the peak current value. 2 The amount of electricity in hydrochloric acid electrolysis (C / dm 2 ) is the total amount of electricity when the aluminum plate is an anode, and is 63C / dm 2 It was.
[0253] (Jh) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda with a caustic soda concentration of 5% by mass and an aluminum ion concentration of 0.5% by mass at a temperature of 60°C. The amount of dissolved aluminum was 0.2 g / m 2 It was.
[0254] (Ji) Desmutting treatment using an acidic aqueous solution The acidic aqueous solution was a wastewater (sulfuric acid concentration 170 g / L and aluminum ion concentration 5 g / L) generated in the anodizing process at a liquid temperature of 35°C, which was sprayed onto the aluminum plate for 4 seconds to perform desmutting.
[0255] (Jj) First stage anodizing The first stage of anodizing was carried out using a direct current anodizing apparatus with the structure shown in Fig. 6. A 170 g / L aqueous sulfuric acid solution was used as the electrolyte, the solution temperature was 50°C, and the current density was 30 A / dm 2 The anodizing process was carried out under the conditions of 0.3 g / m 2 An anodic oxide film was formed.
[0256] (Jk) Pore Widening Treatment The anodized aluminum plate was immersed in an aqueous solution of caustic soda with a caustic soda concentration of 5 mass % and an aluminum ion concentration of 0.5 mass % at 40° C. for 3 seconds to carry out a pore widening treatment.
[0257] (Jl) Second stage anodizing The second stage of anodizing was carried out using a direct current anodizing apparatus with the structure shown in Fig. 6. A 170 g / L aqueous sulfuric acid solution was used as the electrolyte, the solution temperature was 50°C, and the current density was 13 A / dm 2 The anodizing process was carried out under the conditions of 2 An anodic oxide film was formed.
[0258] (Jm) Hydrophilic treatment To ensure hydrophilicity in non-image areas, the aluminum plate was subjected to a silicate treatment by immersing it in a 2.5% by weight aqueous solution of sodium silicate No. 3 at 50°C for 7 seconds. The amount of silicon attached was 8.5 mg / m 2 The average diameter of the micropores was 30 nm. The lightness L* value of the anodized film surface of Support 1 in the L*a*b* color system was 72.3.
[0259] <Preparation of Support 2> An aluminum plate (aluminum alloy plate) of material 1S with a thickness of 0.3 mm was subjected to the following treatments (Fa) to (Fg) to produce a support 2. Note that a water rinsing treatment was performed between all treatment steps, and after the water rinsing treatment, the liquid was removed with a nip roller.
[0260] (Fa) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda with a caustic soda concentration of 26% by mass and an aluminum ion concentration of 6.5% by mass at a temperature of 70°C. The amount of aluminum dissolved on the surface to be subsequently subjected to electrochemical graining treatment was 5 g / m 2 It was.
[0261] (Fb) Desmutting treatment using an acidic aqueous solution As the acidic aqueous solution, an aqueous solution of sulfuric acid having a concentration of 150 g / L and a liquid temperature of 30° C. was sprayed onto the aluminum plate for 3 seconds to carry out a desmutting treatment.
[0262] (Fc) Electrochemical roughening treatment An electrochemical graining treatment was performed using an electrolytic solution with a hydrochloric acid concentration of 14 g / L, an aluminum ion concentration of 13 g / L, and a sulfuric acid concentration of 3 g / L, using an alternating current. The temperature of the electrolytic solution was 30° C. The aluminum ion concentration was adjusted by adding aluminum chloride. The AC waveform is a sine wave with symmetrical positive and negative waveforms, the frequency is 50Hz, the anode reaction time and cathode reaction time in one AC cycle are 1:1, and the current density is 75A / dm at the peak current value of the AC waveform. 2 The total amount of electricity that the aluminum plate receives in the anode reaction is 450 C / dm 2 and electrolytic treatment is 112.5C / dm 2 The current was applied four times, with a four-second interval between each. A carbon electrode was used as the counter electrode for the aluminum plate.
[0263] (Fd) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution of caustic soda with a caustic soda concentration of 5% by mass and an aluminum ion concentration of 0.5% by mass at a temperature of 45°C. The amount of dissolved aluminum on the surface that had been subjected to electrochemical graining treatment was 0.2 g / m 2 It was.
[0264] (Fe) Desmutting treatment using an acidic aqueous solution The acidic aqueous solution, an aqueous solution having a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L at a liquid temperature of 35° C., was sprayed onto the aluminum plate for 3 seconds to carry out a desmutting treatment.
[0265] (Ff) First stage anodizing The first stage of anodizing was carried out using a direct current electrolysis anodizing apparatus with the structure shown in Fig. 6. A 150 g / L phosphoric acid solution was used as the electrolyte, the solution temperature was 35°C, and the current density was 4.5 A / dm 2 Anodizing was performed under the conditions of 1 g / m 2 An anodic oxide film was formed.
[0266] (Fg) Second stage anodizing The second stage of anodizing was carried out using a direct current anodizing apparatus with the structure shown in Fig. 6. A 170 g / L aqueous sulfuric acid solution was used as the electrolyte, the solution temperature was 50°C, and the current density was 13 A / dm 2 The anodizing process was carried out under the conditions of 2 An anodic oxide film of the above was formed. After that, washing with water was performed by spraying. The average diameter of the micropores of the support 2 was 40 nm. The anodic oxide film surface of Support 2 had a lightness L* value of 83.7 in the L*a*b* color system.
[0267] <Preparation of Support 3> An aluminum plate (aluminum alloy plate) of material 1S with a thickness of 0.19 mm was degreased by immersing it in a 40 g / L aqueous solution of sodium hydroxide at 60°C for 8 seconds, and then washed with demineralized water for 2 seconds. The aluminum plate was then immersed in an aqueous solution containing 12 g / L hydrochloric acid and 38 g / L aluminum sulfate (18-hydrate) at a temperature of 33°C and a current of 130 A / dm for 15 seconds using alternating current. 2 After washing with demineralized water for 2 seconds, the aluminum plate was desmutted by etching with a 155 g / L aqueous sulfuric acid solution at 70°C for 4 seconds, and then washed with demineralized water at 25°C for 2 seconds. The aluminum plate was then immersed in a 155 g / L aqueous sulfuric acid solution for 13 seconds at a temperature of 45°C and a current density of 22 A / dm 2 The substrate was anodized at a current density of 100 .mu.m and washed with demineralized water for 2 seconds. The substrate was then treated with a 4 g / L aqueous solution of polyvinyl phosphonic acid at 40°C for 10 seconds, washed with demineralized water at 20°C for 2 seconds, and dried to produce Support 3. Support 3 had a surface roughness Ra of 0.21 μm and an anodized film weight of 4 g / m2. 2The average diameter of the micropores in Support 3 was 7 nm. The anodic oxide film surface of Support 3 had a lightness L* value of 73.5 in the L*a*b* color system.
[0268] <Preparation of Support 4> An aluminum plate (aluminum alloy plate) of material 1S having a thickness of 0.3 mm was subjected to the following treatments (Aa) to (Ag) to produce a support 4. Note that a water rinsing treatment was performed between all treatment steps, and after the water rinsing treatment, the liquid was removed with a nip roller.
[0269] (Aa) Alkaline etching treatment An aluminum plate was etched by spraying an aqueous solution with a caustic soda concentration of 26% by mass, an aluminum ion concentration of 6.5% by mass, and a temperature of 70°C from a sprayer. The etching amount of the surface of the aluminum plate to be subsequently subjected to electrochemical graining treatment was 5 g / m 2 It was.
[0270] (Ab) Desmutting using an acidic aqueous solution As the acidic aqueous solution, an aqueous solution of sulfuric acid having a concentration of 150 g / L and a liquid temperature of 30° C. was sprayed onto the aluminum plate for 3 seconds to carry out a desmutting treatment.
[0271] (Ac) Electrochemical roughening treatment using hydrochloric acid solution An electrochemical graining treatment was performed using an electrolytic solution with a hydrochloric acid concentration of 14 g / L, an aluminum ion concentration of 13 g / L, and a sulfuric acid concentration of 3 g / L, using an alternating current. The temperature of the electrolytic solution was 30° C. The aluminum ion concentration was adjusted by adding aluminum chloride. The AC waveform is a sine wave with symmetrical positive and negative waveforms, the frequency is 50Hz, the anode reaction time and cathode reaction time in one AC cycle are 1:1, and the current density is 75A / dm at the peak current value of the AC waveform. 2 The total amount of electricity that the aluminum plate receives in the anode reaction is 450 C / dm 2 and electrolytic treatment is 112.5C / dm 2The current was applied four times, with a four-second interval between each. A carbon electrode was used as the counter electrode for the aluminum plate.
[0272] (Ad) Alkaline etching treatment An aluminum plate was etched by spraying with an aqueous solution having a caustic soda concentration of 5% by mass, an aluminum ion concentration of 0.5% by mass, and a temperature of 45°C. The amount of etching on the electrochemically roughened surface of the aluminum plate was 0.2 g / m 2 It was.
[0273] (Ae) Desmutting treatment using an acidic aqueous solution The acidic aqueous solution was a waste liquid generated in the anodizing process (aqueous solution with a sulfuric acid concentration of 170 g / L and an aluminum ion concentration of 5 g / L) at a liquid temperature of 30°C, which was sprayed onto the aluminum plate for 3 seconds to perform a desmutting treatment.
[0274] (Af) Anodizing Anodizing was performed using a direct current anodizing apparatus with the structure shown in Figure 6. A 170 g / L aqueous sulfuric acid solution was used as the electrolyte, and the solution temperature was 50°C and the current density was 30 A / dm 2 The anodizing process was carried out under the conditions of 2.4 g / m 2 An anodic oxide film was formed. In an anodizing treatment apparatus 410 shown in Fig. 6, an aluminum sheet 416 is transported as indicated by an arrow in Fig. 6. In a power supply tank 412 in which an electrolytic solution 418 is stored, the aluminum sheet 416 is charged (+) by a power supply electrode 420. Then, in the power supply tank 412, the aluminum sheet 416 is transported upward by a roller 422, and its direction is changed downward by a nip roller 424, and then the aluminum sheet 416 is transported toward an electrolytic treatment tank 414 in which an electrolytic solution 426 is stored, and its direction is changed horizontally by a roller 428. Next, the aluminum sheet 416 is charged (-) by an electrolytic electrode 430, so that an anodized film is formed on the surface of the aluminum sheet 416, and the aluminum sheet 416 that leaves the electrolytic treatment tank 414 is transported to a subsequent process. In the anodizing treatment device 410, the roller 422, the nip roller 424, and the roller 428 constitute a direction changing means, and the aluminum sheet 416 is transported in a mountain shape and an inverted U shape by the rollers 422, 424, and 428 in the space between the power supply tank 412 and the electrolytic treatment tank 414. The power supply electrode 420 and the electrolytic electrode 430 are connected to a DC power source 434.
[0275] (Ag)Pore-wide processing The anodized aluminum plate was immersed in an aqueous solution of caustic soda with a caustic soda concentration of 5% by mass and an aluminum ion concentration of 0.5% by mass at 40°C for 3 seconds to perform a pore widening treatment. It was then washed with water by spraying. The average diameter of the micropores was 30 nm. The anodic oxide film surface of Support 4 had a lightness L* value of 81.4 in the L*a*b* color system.
[0276] <Formation of Undercoat Layer 1> On the support, the undercoat layer coating solution (1) having the following composition was applied in a dry coating amount of 26 mg / m 2 The undercoat layer 1 was formed by coating so as to become
[0277] (Undercoat layer coating solution (1)) Undercoat layer compound (2) (structure below) 0.13 parts Hydroxyethyliminodiacetic acid 0.05 parts Tetrasodium ethylenediaminetetraacetate 0.05 parts Polyoxyethylene lauryl ether 0.03 parts ·Wednesday 61.39 parts
[0278] [ka]
[0279] The numerical value in the right subscript of each of the parentheses for each of the structural units in the above undercoat layer compound (2) indicates the mass ratio, and the numerical value in the right subscript of each of the parentheses for the ethyleneoxy unit indicates the number of repetitions.
[0280] <Formation of Undercoat Layer 2> On the support, the undercoat layer coating solution (2) having the following composition was applied in a dry coating amount of 93 mg / m 2 The undercoat layer 2 was formed by coating so as to become
[0281] (Undercoat layer coating solution (2)) Specific hydroxy acid compound 0.90 parts Polyoxyethylene lauryl ether 0.03 parts ·Wednesday 61.39 parts
[0282] <Formation of Undercoat Layer 3> On the support, the undercoat layer coating solution (3) having the following composition was applied in a dry coating amount of 11 mg / m 2 The undercoat layer 3 was formed by coating so as to become
[0283] (Undercoat layer coating solution (3)) Undercoat layer compound (3) (structure below) 0.13 parts Polyoxyethylene lauryl ether 0.03 parts ·Wednesday 61.39 parts
[0284] [ka]
[0285] <Formation of Image Recording Layer 1> An image recording layer coating solution (1) having the following composition was applied with a bar and dried in an oven at 100° C. for 60 seconds to form an image recording layer 1 having a thickness of 1.2 μm. The image recording layer coating solution (1) was obtained by mixing and stirring the following photosensitive solution (1) and microgel solution (1) immediately before coating.
[0286] (Photosensitive liquid (1)) Binder polymer (6) 23% by mass solution in 1-methoxy-2-propanol (structure below) 0.2891 copies Binder polymer (7) 23% by mass solution in 1-methoxy-2-propanol (structure below) 0.4574 copies Infrared absorber (1) (structure below) 0.0278 parts Borate compounds (1) (sodium tetraphenylborate) 0.015 parts Polymerization initiator (1) (structure below) 0.2348 parts Polymerizable compound (1) (tris(acryloyloxyethyl)isocyanurate, NK Ester A-9300 40% 2-butanone solution, manufactured by Shin-Nakamura Chemical Co., Ltd.) 0.2875 copies Low molecular weight hydrophilic compound (1) (tris(2-hydroxyethyl)isocyanurate) 0.0287 parts Low molecular weight hydrophilic compound (2) (trimethylglycine) 0.0147 parts Anionic surfactant 1 30% by weight aqueous solution (structure below) 0.25 parts Ultraviolet absorber (1) (TINUVIN 405, manufactured by BASF Ltd.) (structure below) 0.04 parts Fluorine-based surfactant (1) (structure below) 0.004 parts Phosphonium compound (1) (structure below) 0.020 parts 5.346 parts 2-butanone 3.128 parts 1-methoxy-2-propanol Methanol 0.964 parts ·Pure water 0.036 part
[0287] (Microgel Liquid (1)) ·Microgel (1) (solid content 21.8% by mass) 2.243 parts 0.600 parts 1-methoxy-2-propanol
[0288] (Preparation of Microgel (1)) The method for preparing the microgel (1) used in the above microgel solution is described below.
[0289] <Preparation of polyisocyanate compound (1)> To a suspension of 17.78 parts (80 molar equivalents) of isophorone diisocyanate and 7.35 parts (20 molar equivalents) of the following polyhydric phenol compound (1) in ethyl acetate (25.31 parts), 0.043 parts of bismuth tris(2-ethylhexanoate) (Neostan U-600, manufactured by Nitto Kasei Co., Ltd.) was added and stirred. When the heat generation subsided, the reaction temperature was set to 50°C, and the mixture was stirred for 3 hours to obtain an ethyl acetate solution (50% by mass) of the polyhydric isocyanate compound (1).
[0290] [ka]
[0291] <Preparation of Microgel (1)> The following oil phase components and water phase components were mixed and emulsified for 10 minutes at 12,000 rpm using a homogenizer. The resulting emulsion was stirred at 45°C for 4 hours, and then 5.20 parts of a 10% by mass aqueous solution of 1,8-diazabicyclo[5.4.0]undec-7-ene-octylate (U-CAT SA102, manufactured by San-Apro Co., Ltd.) was added, stirred at room temperature for 30 minutes, and allowed to stand at 45°C for 24 hours. The solid content was adjusted to 21.8% by mass with distilled water to obtain an aqueous dispersion of microgel (4). The volume average particle size was measured by a light scattering method using a dynamic light scattering particle size distribution measuring device LB-500 (manufactured by Horiba, Ltd.), and was found to be 0.28 μm.
[0292] (Oily Phase Components) (Component 1) Ethyl acetate 12.0 parts (Component 2) An adduct obtained by adding trimethylolpropane (6 moles) and xylylene diisocyanate (18 moles) to which was added polyoxyethylene (1 mole, number of repeating oxyethylene units: 90) terminated with methyl (50% by mass in ethyl acetate solution, manufactured by Mitsui Chemicals, Inc.) 3.76 copies (Component 3) Polyisocyanate compound (1) (as a 50% by mass solution in ethyl acetate) 15.0 copies (Component 4) 11.54 parts of 65% by weight solution of dipentaerythritol pentaacrylate (SR-399, manufactured by Sartomer Corporation) in ethyl acetate (Component 5) 4.42 parts of a 10% solution of sulfonate surfactant (Paionin A-41-C, Takemoto Oil Co., Ltd.) in ethyl acetate
[0293] (Aqueous phase component) 46.87 parts distilled water
[0294] <Synthesis of binder polymer (6)> 78.0 g of 1-methoxy-2-propanol was weighed into a three-neck flask and heated to 70° C. under a nitrogen stream. A mixed solution consisting of 52.1 g of Blenmer PME-100 (methoxydiethylene glycol monomethacrylate, manufactured by Nippon Oil & Fats Co., Ltd.), 21.8 g of methyl methacrylate, 14.2 g of methacrylic acid, 2.15 g of hexakis (3-mercaptopropionic acid) dipentaerythritol, 0.38 g of V-601 (2,2'-azobis (isobutyric acid) dimethyl, manufactured by Wako Pure Chemical Industries, Ltd.), and 54 g of 1-methoxy-2-propanol was added dropwise to this reaction vessel over 2 hours and 30 minutes. After the dropwise addition was completed, the temperature was raised to 80° C., and the reaction was continued for another 2 hours. A mixed solution consisting of 0.04 g of V-601 and 4 g of 1-methoxy-2-propanol was added, and the temperature was raised to 90° C., and the reaction was continued for 2.5 hours. After completion of the reaction, the reaction solution was cooled to room temperature. To the above reaction solution, 137.2 g of 1-methoxy-2-propanol, 0.24 g of 4-hydroxytetramethylpiperidine-N-oxide, 26.0 g of glycidyl methacrylate, and 3.0 g of tetraethylammonium bromide were added and thoroughly stirred, and then heated at 90°C. After 18 hours, the reaction solution was cooled to room temperature (25° C.) and then diluted with 99.4 g of 1-methoxy-2-propanol. The binder polymer (6) thus obtained had a solid content concentration of 23% by mass and a polystyrene-equivalent weight average molecular weight of 35,000 as measured by GPC.
[0295] [ka]
[0296] <Synthesis of binder polymer (7)> 78.00 g of 1-methoxy-2-propanol was weighed into a three-neck flask and heated to 70° C. under a nitrogen stream. A mixed solution consisting of 52.8 g of Blenmer PME-100 (methoxydiethylene glycol monomethacrylate, manufactured by Nippon Oil & Fats Co., Ltd.), 2.8 g of methyl methacrylate, 25.0 g of methacrylic acid, 6.4 g of hexakis (3-mercaptopropionic acid) dipentaerythritol, 1.1 g of V-601 (2,2'-azobis (isobutyric acid) dimethyl, manufactured by Wako Pure Chemical Industries, Ltd.), and 55 g of 1-methoxy-2-propanol was added dropwise to this reaction vessel over 2 hours and 30 minutes. After the dropwise addition, the temperature was raised to 80° C., and the reaction was continued for another 2 hours. After 2 hours, a mixed solution consisting of 0.11 g of V-601 and 1 g of 1-methoxy-2-propanol was added, and the temperature was raised to 90° C., and the reaction was continued for 2.5 hours. After the reaction was completed, the reaction solution was cooled to room temperature. To the above reaction solution, 177.2 g of 1-methoxy-2-propanol, 0.28 g of 4-hydroxytetramethylpiperidine-N-oxide, 46.0 g of glycidyl methacrylate, and 3.4 g of tetrabutylammonium bromide were added and thoroughly stirred, and then heated at 90°C. After 18 hours, the reaction solution was cooled to room temperature (25° C.) and then diluted with 0.06 g of 4-methoxyphenol and 114.5 g of 1-methoxy-2-propanol. The binder polymer (7) thus obtained had a solid content concentration of 23% by mass and a weight average molecular weight of 15,000 in terms of polystyrene measured by GPC.
[0297] [ka]
[0298] [ka]
[0299] [ka]
[0300] <Formation of image recording layer 2> An image recording layer coating solution (2) having the following composition was applied with a bar and then dried in an oven at 70° C. for 60 seconds to form an image recording layer 2 with a thickness of 0.6 μm.
[0301] (Image recording layer coating liquid (2)) ·Polymerizable compound 1*1 0.15 part ·Polymerizable compound 2*2 0.1 part Graft copolymer 2*3 0.825 parts ·Klucel M*4 0.020 parts ·Irgacure250*5 0.032 parts Infrared absorber 1 (structure below) 0.02 parts Sodium tetraphenylborate 0.03 parts ·Byk 336*6 0.015 parts ·Black-XV*7 0.04 parts 7.470 parts n-propanol ·Wednesday 1.868 parts *1: UA510H (manufactured by Kyoeisha Chemical Co., Ltd., a reaction product of dipentaerythritol pentaacrylate and hexamethylene diisocyanate) *2: ATM-4E (manufactured by Shin-Nakamura Chemical Co., Ltd., ethoxylated pentaerythritol tetraacrylate) *3: Graft copolymer 2 is a polymer particle of a graft copolymer of poly(ethylene glycol) methyl ether methacrylate / styrene / acrylonitrile = 10:9:81, and is a dispersion containing 24% by mass in a solvent of n-propanol / water with a mass ratio of 80 / 20. The volume average particle size is 193 nm. *4: Klucel M refers to hydroxypropyl cellulose available from Hercules. *5: Irgacure 250 is an iodonium salt available from Ciba Specialty Chemicals as a 75% propylene carbonate solution and has the formula iodonium, (4-methylphenyl) [4-(2-methylpropyl) phenyl],-hexafluorophosphate. *6:Byk 336 is a modified dimethylpolysiloxane copolymer available from Byk Chemie in a 25% xylene / methoxypropyl acetate solution. *7: Black-XV (Compound below, manufactured by Yamamoto Chemical Industries, Ltd.)
[0302] [ka]
[0303] <Formation of image recording layer 3> An aqueous coating solution for the image recording layer containing the above thermoplastic polymer particles, infrared absorbing agent and polyacrylic acid was prepared, the pH was adjusted to 3.6, and then the solution was coated on a support and dried at 50° C. for 1 minute to form an image recording layer 3. The coating amount of each component after drying is shown below.
[0304] Thermoplastic polymer particles 0.7g / m 2 Infrared absorber IR-01 1.20 x 10 -4 g / m 2 Polyacrylic acid 0.09g / m 2
[0305] The thermoplastic polymer particles, infrared absorbing agent IR-01, and polyacrylic acid used in the image recording layer coating liquid are as shown below.
[0306] Thermoplastic polymer particles: styrene / acrylonitrile copolymer (molar ratio 50 / 50), Tg: 99°C, volume average particle size: 60 nm Infrared absorbent IR-01: Infrared absorbent with the following structure
[0307] [ka]
[0308] Polyacrylic acid Mw: 250,000
[0309] <Formation of Image Recording Layer 4> An image recording layer coating solution (4) having the following composition was applied with a bar and dried in an oven at 100° C. for 60 seconds to form an image recording layer 4 having a thickness of 0.6 μm.
[0310] (Image recording layer coating liquid (4)) Infrared absorber 4 (structure below) 0.030 parts Polymerization initiator I (structure below) 0.032 parts Polymerizable compound (1) A-9300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) (structure shown below) 0.05 part Polymerizable compound (2) A-DPH (manufactured by Shin-Nakamura Chemical Co., Ltd.) (structure shown below) 0.05 part Binder polymer 3 (see below) 0.825 parts Surfactant BYK306 (Byk Chemie) 0.008 parts 8.609 parts of 1-methoxy-2-propanol Methyl ethyl ketone 1.091 parts
[0311] [ka]
[0312] [ka]
[0313] [ka]
[0314] [ka]
[0315] (Synthesis of binder polymer 3) 300g of methyl ethyl ketone was placed in a three-neck flask and heated to 80°C under a nitrogen stream. A mixed solution consisting of 50.0g of the following compound 1, 30.0g of the following compound 2, 20.0g of the following compound 3, 0.7g of AIBN (azobisisobutyronitrile), and 100g of methyl ethyl ketone was added dropwise to this reaction vessel over 30 minutes. After the dropwise addition was completed, the reaction was continued for another 7.5 hours. Then, 0.3g of AIBN was added, and the reaction was continued for another 12 hours. After the reaction was completed, the reaction liquid was cooled to room temperature to obtain binder polymer 3. The weight average molecular weight of the obtained binder polymer 3 was 75,000.
[0316] [ka]
[0317] <Formation of Image Recording Layer 5> An image recording layer coating solution (5) having the following composition was applied with a bar and dried in an oven at 70° C. for 60 seconds to form an image recording layer 5 having a thickness of 0.6 μm.
[0318] (Image recording layer coating solution (5)) To the above image recording layer coating solution (2), 0.093 parts of Art Pearl J-6PF (average particle size: 4 μm) (highly crosslinked acrylic resin, manufactured by Negami Chemical Industries, Ltd.) was added to prepare an image recording layer coating solution.
[0319] <Formation of Non-Photosensitive Layer 6> A non-photosensitive layer coating solution (6) having the following composition was applied with a bar and dried in an oven at 100° C. for 60 seconds to form a non-photosensitive layer 6 having a thickness of 0.05 μm.
[0320] (Non-photosensitive layer coating solution (6)) Nonionic surfactant 1 (structure below) 0.02 parts Coloring agent (OIL YELLOW 105, Orient Chemical Industry Co., Ltd.) 0.015 parts Methyl ethyl ketone 5.587 parts 3.725 parts 1-methoxy-2-propanol Methanol 3.104 parts
[0321] [ka]
[0322] <Formation of protective layer 1> A protective layer coating solution (1) having the following composition was applied with a bar and dried in an oven at 120° C. for 60 seconds to form a protective layer 1 having a thickness of 0.18 μm.
[0323] (Protective Layer Coating Solution (1)) Inorganic layered compound dispersion (1) (see below) 2.212 parts Polyvinyl alcohol (Gohselan L-3266, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., sulfonic acid modified, saponification degree 85 mol%), 6 mass% aqueous solution 1.440 copies Surfactant (Paionin A-32-B (see below), Takemoto Oil Co., Ltd.) 40% by weight aqueous solution) 0.014 parts Surfactant (Surfynol 465 (see below), manufactured by Nissin Chemical Co., Ltd.) 0.006 parts ·Pure water 3.955 parts
[0324] [ka]
[0325] (Preparation of Inorganic Layered Compound Dispersion (1)) 6.4 parts of synthetic mica Somasif ME-100 (manufactured by Co-op Chemical Co., Ltd.) was added to 193.6 parts of ion-exchanged water, and dispersed using a homogenizer until the volume average particle size (laser scattering method) was 3 μm, to prepare an inorganic layered compound dispersion (1). The aspect ratio of the dispersed particles was 100 or more.
[0326] <Formation of protective layer 2> A protective layer coating solution (2) having the following composition was applied with a bar and dried in an oven at 120° C. for 60 seconds to form a protective layer 2 having a thickness of 0.8 μm.
[0327] (Protective Layer Coating Solution (2)) Polyvinyl alcohol (Poval PVA105, manufactured by Kuraray Co., Ltd.) 0.6 parts Polyethylene glycol (PEG4000, manufactured by Tokyo Chemical Industry Co., Ltd.) 0.39 parts Surfactant (Rapisol A-80 (see below), manufactured by NOF Corp.) 0.01 part ·Pure water: 9 parts
[0328] [ka]
[0329] <Formation of protective layer 3> A protective layer coating solution (3) having the following composition was applied with a bar and dried in an oven at 120° C. for 60 seconds to form a protective layer 3 having a thickness of 0.5 μm.
[0330] (Protective Layer Coating Solution (3)) Polyvinyl alcohol (Gohselan L-3266, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., sulfonic acid modified, saponification degree 85 mol%) 0.500 parts Surfactant (Rapisol A-80 (above) 0.024 parts Anionic surfactant 1 (above) 0.333 parts ·Pure water 18,000 parts
[0331] [Preparation of printing plate] The above-mentioned supports, undercoat layers, image recording layers, non-photosensitive layers and protective layers were combined as shown in Table A to prepare the lithographic printing plate precursors of Examples 1 to 43 and 45, the discardable plate precursors of Examples 46 to 48, and the lithographic printing plate precursors of Comparative Examples 1 to 6. The lithographic printing plate precursor of Example 44 was prepared by combining the above-mentioned support, undercoat layer, image recording layer and protective layer as shown in Table A, and further forming the following backcoat layer 1. The throwaway plate master of Example 49 was prepared by using the same combination of the support, undercoat layer, image recording layer and protective layer as in Example 46, and further forming the following backcoat layer 2.
[0332] <Formation of backcoat layer 1> A backcoat layer coating solution (1) having the following composition was applied with a bar to the side of the support opposite to the side having the specific component layer (protective layer) and dried at 100°C for 30 seconds to form a backcoat layer 1 having a thickness of 1.2 μm.
[0333] (Backcoat Layer Coating Solution (1)) Acrylic resin (BR-605, manufactured by Mitsubishi Chemical Corporation) 11.072 copies 0.500 parts of organic smectite (Sumecton-SEN (tabular particles), manufactured by Kunimine Kogyo Co., Ltd.) Acrylic particles (Art Pearl J-6PF, manufactured by Negami Chemical Industries, Ltd.) 0.975 copies Surfactant (Rheodol TW-S106V (polyoxyethylene (6) sorbitan monostearate), manufactured by Kao Corporation) 0.250 parts 74.123 parts 2-butanone 8.720 parts of 1-methoxy-2-propanol Methanol 4.360 parts
[0334] <Formation of backcoat layer 2> A backcoat layer coating solution (2) having the following composition was applied with a bar to the side of the support opposite to the side having the specific component layer (protective layer) and dried at 100°C for 30 seconds to form a backcoat layer 2 having a thickness of 1.2 μm.
[0335] (Backcoat Layer Coating Solution (2)) Acrylic resin (BR-73, manufactured by Mitsubishi Chemical Corporation) 11.072 copies 0.500 parts of organic smectite (Sumecton-SEN (tabular particles), manufactured by Kunimine Kogyo Co., Ltd.) Acrylic particles (Art Pearl J-6PF, manufactured by Negami Chemical Industries, Ltd.) 0.975 copies Surfactant (Rheodol TW-S106V (polyoxyethylene (6) sorbitan monostearate), manufactured by Kao Corporation) 0.250 parts 74.123 parts 2-butanone 8.720 parts of 1-methoxy-2-propanol Methanol 4.360 parts
[0336] For the lithographic printing plate precursor of Comparative Example 6, after coating the image recording layer, without drying, an aqueous solution of the comparative compound was coated using a coating device 2NL04 manufactured by Heishin Kikai Co., Ltd. That is, the clearance of the coating device was fixed at 0.3 m, and the amount of liquid sent was adjusted to coat the aqueous solution of the comparative compound in a width of 6 mm at a position 3 cm from the edge so as to obtain the content of the comparative compound shown in Table A. Then, it was oven-dried at 100° C. for 60 seconds.
[0337] [Table 1]
[0338] [Table 2]
[0339] In Table A, the layer to which a specific hydroxy acid compound or a comparative compound is added represents a constituent layer (undercoat layer, image recording layer, non-photosensitive layer, protective layer) of a printing plate precursor containing a specific hydroxy acid compound or a comparative compound. The constituent layer can be formed by adding the specific hydroxy acid compound or the comparative compound to a coating solution of the corresponding constituent layer to prepare a coating solution and coating the coating solution. In Comparative Example 6, the amount of the comparative compound (citric acid) added is described as 200 / 0, which means that the amount of the comparative compound added in the edge region is 200 mg / m 2 , the amount of the comparative compound added in the region other than the end is 0 mg / m 2 This indicates that.
[0340] In the lithographic printing plate precursor of Example 44, the backcoat layer contained resin particles having an average particle diameter of 4 μm, and the arithmetic mean height Sa of the outermost layer (backcoat layer) surface on the side opposite to the side having the specific component layer was 1.8 μm. In the lithographic printing plate precursor of Example 45, the image recording layer contained resin particles having an average particle diameter of 4 μm, and the arithmetic mean height Sa of the outermost layer (image recording layer) surface on the side having the specific component layer (undercoat layer) was 1.5 μm. In the throwaway plate master of Example 49, the backcoat layer contained resin particles with an average particle diameter of 4 μm, and the arithmetic mean height Sa of the outermost layer (backcoat layer) surface on the side opposite to the side having the specific component layer was 1.8 μm.
[0341] <Cutting the printing plate> The printing plate master was cut using a rotary blade as shown in FIG. 4, with the gap between the upper and lower cutting blades, the amount of engagement, and the blade angle adjusted to form a droop shape at the edge. The lithographic printing plate precursor of Comparative Example 6 was cut at the center of a 6 mm wide area where the aqueous solution of the comparative compound was applied, to obtain a lithographic printing plate precursor having a sagging shape at the edge and a 3 mm wide area of the comparative compound. The sagging amount X and sagging width Y of the sagging shape are shown in Table A.
[0342] [Evaluation of printing plate] The printing plate precursor was evaluated for edge stain prevention and image forming properties at the edge as follows.
[0343] <Prevents edge staining, no aging> The lithographic printing plate precursors of Examples 1 to 45 and Comparative Examples 1 to 6 were exposed using a Luxcel PLATESETTER T-6000III equipped with an infrared semiconductor laser manufactured by FUJIFILM Corporation under the conditions of an outer drum rotation speed of 1,000 rpm, a laser output of 70%, and a resolution of 2,400 dpi. A chart including a solid image, a 50% halftone dot, and a non-image area was used as the exposed image. The image-exposed lithographic printing plate precursor and the throwaway plate precursors of Examples 46 to 49 were mounted on an offset rotary press manufactured by Tokyo Machine Works, Ltd., and printed on newsprint at a speed of 100,000 sheets / hour using Soybee KKST-S (red) manufactured by Inktec Co., Ltd. as newsprint ink and Toyo ALKY manufactured by Toyo Ink Co., Ltd. as dampening water. The 1,000th printed sheet was sampled at a water level 1.1 times the water level for eliminating background staining, and the degree of linear staining caused by the edge of the printing plate precursor was evaluated according to the following criteria. The results are shown in Table A as edge staining prevention and no aging. 5: Not dirty at all 4: Intermediate level between 5 and 3 3: Slightly dirty but acceptable level 2: Intermediate level between 3 and 1 (acceptable level) 1: Significantly dirty and unacceptable
[0344] <Edge stain prevention, after aging> The printing plate precursors of Examples 1 to 49 and Comparative Examples 1 to 6 were left for 10 days in an environment with a relative humidity of 70% and a temperature of 25°C (corresponding to being left for 12 months in a normal environment (relative humidity of 50% and a temperature of 25°C)). Thereafter, the edge stain prevention property was evaluated in the same manner as above. The results are shown in Table A as edge stain prevention property after aging.
[0345] <Image forming properties at the edge> The lithographic printing plate precursors of Examples 1 to 45 and Comparative Examples 1 to 6, which had been image-exposed in the same manner as in the evaluation of edge stain prevention and no aging, were mounted on an offset rotary printing press manufactured by Tokyo Kikai Seisakusho Co., Ltd., and printed on newsprint at a speed of 100,000 sheets / hour using Soybee KKST-S (red) manufactured by Inktec Co., Ltd. as the newspaper printing ink and Eco7 N-1 manufactured by Sakata Inx Co., Ltd. as the dampening water. The 1,000th, 10,000th, 50,000th and 100,000th prints were sampled, and the image formability in the region up to 1 mm inward from the edge of the printing plate precursor was evaluated according to the following criteria. 5: Images are still printed even after 100,000 prints. 4: Images are still printed even after 50,000 prints. 3: The image is still printed even after 10,000 prints. 2: The image is still printed even after 1,000 prints. 1: After printing 1,000 sheets, the image is not printed.
[0346] From the results shown in Table A, it can be seen that the printing plate precursor containing the specific hydroxy acid compound according to the present invention exhibits excellent edge stain prevention properties not only after production but also after aging, and the edge stain prevention properties are well maintained for a long period of time. In contrast, the printing plate precursors of Comparative Examples 1-5 containing comparative compounds other than the specific hydroxy acid compound have poor edge stain prevention properties after aging. The citric acid used in Comparative Example 4 is a hydroxy acid having one hydroxyl group, and has poor edge stain prevention properties after aging. It can be said that the fact that excellent edge stain prevention properties are maintained even after aging due to the difference in the number of hydroxyl groups in this way is an unexpected and surprising effect. It is also seen that the planographic printing plate precursor according to the present invention has good image forming properties at the edges. In contrast, the planographic printing plate precursor of Comparative Example 6 has poor image forming properties at the edges. This effect of good image forming properties at the edges can also be said to be an unexpected and surprising effect caused by the difference in the number of hydroxyl groups. In addition, in the embodiment 1~ 12. 14~ 28, 30~ 33, 37~ 40、44~46、49 are reference examples 1~ 12. 14~ 28, 30~ 33, 37~ 40 、44~46、49 shall be read as follows. [Industrial Applicability]
[0347] According to the present invention, it is possible to provide an on-press development type printing original plate in which edge contamination is prevented not only after production but also after aging, a method for making a printing plate using an on-press development type printing original plate, and a printing method using an on-press development type printing original plate. Furthermore, according to the present invention, it is possible to provide an on-press development type lithographic printing plate precursor in which deterioration of image formability in edge regions is suppressed.
[0348] This application is based on a Japanese patent application (Patent Application No. 2020-011914) filed on January 28, 2020, and a Japanese patent application (Patent Application No. 2020-103357) filed on June 15, 2020, the contents of which are incorporated by reference into this application. [Explanation of symbols]
[0349] 1 Planographic printing plate original plate 1a Image recording layer surface 1b Support surface 1c end face 2 Sauce 10 Cutting blade 10a Upper cutting blade 10b Upper cutting blade 11 Rotation axis 20 Cutting blade 20a Lower cutting blade 20b Lower cutting blade 21 Rotation axis 30 Original printing plate 31 Aluminum plate 32, 34 Roller brush 33 Polishing slurry 35, 36, 37, 38 Support rollers 50 Main electrolyzer 51 AC power supply 52 Radial drum roller 53a, 53b Main pole 54 Electrolyte supply port 55 Electrolyte 56 Slit 57 Electrolyte passage 58 Auxiliary anode 60 Auxiliary anode tank 410 Anodizing Equipment 412 Power tank 414 Electrolytic treatment tank 416 Aluminum Plate 418, 426 Electrolyte 420 Power supply electrode 422,428 Lola 424 Nip Roller 430 Electrolytic electrode 432 Tank wall 434 DC power supply B. Boundary between the image recording layer surface and the support W Aluminum Plate X Droop amount Y sag width
Claims
1. An on-press development type printing plate precursor having at least one constituent layer on an aluminum support having an anodized film, wherein an edge of the on-press development type printing plate precursor has a drooped shape, and the at least one constituent layer contains a hydroxy acid compound having two or more hydroxyl groups, has a molecular weight of 60 to 300, and has a solubility in water at 20°C of 10 g / L or more, and the content of the water-soluble compound is substantially uniform within the plane of the constituent layer, the on-press development type printing plate precursor has an image recording layer, The on-press development type printing plate precursor has a protective layer, The on-press development type printing plate precursor, wherein the constituent layer containing the hydroxy acid compound is a protective layer.
2. 2. The on-press development type printing plate precursor according to claim 1, which has an undercoat layer.
3. 3. The on-press development type printing plate precursor according to claim 1, wherein the protective layer contains a polyvinyl alcohol resin.
4. 4. The on-press development type printing plate precursor according to claim 1, wherein the image recording layer contains an infrared absorbing agent, a polymerization initiator, a polymerizable compound, and a polymer compound.
5. 5. The on-press development type printing plate precursor according to claim 4, wherein the polymer compound contains a structural unit derived from a styrene compound and / or a structural unit derived from an acrylonitrile compound.
6. 6. The on-press development type printing plate precursor according to claim 5, wherein in the polymer compound containing a structural unit derived from a styrene compound and a structural unit derived from an acrylonitrile compound, a compositional ratio of the structural unit derived from a styrene compound to the structural unit derived from an acrylonitrile compound is 4:1 to 1:
4.
7. The on-press development type printing plate precursor according to any one of claims 4 to 6, wherein the polymer compound is a polymer particle.
8. 8. The on-press development type printing plate precursor according to claim 7, wherein the polymer particles are thermoplastic particles.
9. An on-press development type printing plate precursor having at least one constituent layer on an aluminum support having an anodized film, wherein an edge of the on-press development type printing plate precursor has a drooped shape, and the at least one constituent layer contains a hydroxy acid compound having two or more hydroxyl groups, has a molecular weight of 60 to 300, and has a solubility in water at 20°C of 10 g / L or more, and the content of the water-soluble compound is substantially uniform within the plane of the constituent layer, The on-press development type printing plate precursor has a non-photosensitive layer, and all of the constituent layers are non-photosensitive, The on-press development type printing plate precursor has an undercoat layer.
10. The on-press development type printing plate precursor according to claim 9, which has a protective layer.
11. The on-press development type printing plate precursor according to claim 10, wherein the protective layer contains a polyvinyl alcohol resin.
12. The on-press development type printing plate precursor according to any one of claims 9 to 11, wherein the constituent layer containing the hydroxy acid compound is a non-photosensitive layer.
13. The on-press development type printing plate precursor according to any one of claims 9 to 11, wherein the layer containing a hydroxy acid compound is an undercoat layer.
14. The on-press development type printing plate precursor according to claim 10 or 11, wherein the layer containing the hydroxy acid compound is a protective layer.
15. The on-press development type printing plate precursor according to any one of claims 1 to 14, wherein the hydroxy acid compound has a ClogP value of 0.5 or less.
16. The on-press development type printing plate precursor according to any one of claims 1 to 15, wherein the molecular weight of the hydroxy acid compound is 1,000 or less.
17. The content of the hydroxy acid compound is 10 to 200 mg / m 2 The on-press development type printing plate precursor according to any one of claims 1 to 16,
18. The on-press development type printing plate precursor according to any one of claims 1 to 17, wherein the arithmetic mean height Sa of the outermost layer surface on the side opposite to the side having the constituent layer containing a hydroxy acid compound is 0.3 to 20 µm.
19. The on-press development type printing plate precursor according to any one of claims 1 to 18, wherein the arithmetic mean height Sa of the outermost layer surface on the side having the component layer containing a hydroxy acid compound is 0.3 to 20 µm.
20. The on-press development type printing plate precursor according to any one of claims 1 to 19, wherein an average diameter of micropores on a surface of the anodized coating is 10 to 100 nm, and a lightness L* value in the L*a*b* color system of a surface of the anodized coating on a side of a component layer containing a hydroxy acid compound is 60 to 100.
21. 21. The on-press development type printing plate precursor according to any one of claims 1 to 20, wherein the micropores in the anodized film are composed of large diameter pores extending 10 nm to 1,000 nm in a depth direction from a surface of the anodized film, and small diameter pores that communicate with bottoms of the large diameter pores and extend 20 nm to 2,000 nm in a depth direction from the communication positions, the large diameter pores have an average diameter of 15 nm to 100 nm at the surface of the anodized film, and the small diameter pores have an average diameter of 13 nm or less at the communication positions.
22. The on-press development type printing plate precursor according to any one of claims 1 to 21, wherein the sagging shape of the end portion of the on-press development type printing plate precursor has a sagging amount X of 25 to 150 μm and a sagging width Y of 70 to 300 μm.
23. 9. A method for preparing a printing plate, comprising: a step of imagewise exposing the on-press development type printing plate precursor according to any one of claims 1 to 8; and a step of supplying at least one of printing ink and dampening water on a printing press to remove an unexposed area of an image recording layer in the imagewise exposed on-press development type printing plate precursor.
24. A printing method comprising: a step of supplying at least one of printing ink and dampening water to the on-press development type printing plate precursor according to any one of claims 9 to 14 on a printing press to remove a non-photosensitive layer in the on-press development type printing plate precursor to prepare a throwaway plate; and a step of carrying out printing using the prepared throwaway plate.
Citation Information
Patent Citations
Lithographic printing plate dummy plate, printing method using lithographic printing plate dummy plate, and, plate making method of lithographic printing plate dummy plate
JP2017136844A
Lithographic printing plate original plate and method for producing the same, lithographic printing plate original plate laminate, and lithographic printing method
JP2019064269A
A lithographic printing plate precursor comprising graphite oxide
US20180207925A1
Lithographic printing plate master, manufacturing method therefor, and printing method using same
WO2016052443A1
Lithographic printing original plate, method for manufacturing same, and printing method using same
WO2016129374A1
